World Health Organization attribution of burden of foodborne diseases to transmission pathways and foods - Sara M. Pires; Lapo Mughini-Gras; Sandra Hoffmann; Kunihiro Kubota; Shannon E. Majowicz; Martyn D. Kirk; Lucy J. Robertson; Paul R. Torgerson; Lea S. Jakobsen; Antonio Agudo; Li Bai; Tety Rachmawati; et al. (Food Research International, 2026)

Electrification and renovation in the EU building sector decarbonization: a multi-model comparison - Ece Özer; Lukas Kranzl; Andreas Müller; Şirin Alibaş; Robin Hasse; Theofano Fotiou; Robert Pietzcker; Behnam Zakeri (Energy and Buildings, 2026)

Ancestry informative genetic variants associated with tobacco metabolic and detoxification capacity measured by 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) among smokers - Oladimeji Lanade; Zhongxuan He; Yan Zhou; Elizabeth Blackman; Denise Gibbs; Sharon Harrison; Karthik Devarajan; Mark Andrake; Roland L. Dunbrack; Gerald Nkogbu; Aditi Wagh; Michael Slifker; et al. (Archives of Toxicology, 2026)
Tobacco use remains the leading preventable cause of cancer mortality worldwide, with marked disparities in cancer incidence and outcomes across racial and ethnic groups. This study investigates the genetic determinants of tobacco carcinogen metabolism among smokers, focusing on ancestry-informative markers (AIMs) near genes involved in metabolic activation (Phase I), detoxification (Phase II), and transport (Phase III) of tobacco-specific carcinogens. Using data from 274 smokers recruited in the United States and the Caribbean, we measured urinary NNAL (a metabolite of NNK) to classify metabolic phenotypes and performed genotyping with a customized array enriched for AIMs. Most participants (94%) were classified as poor metabolizers of NNAL, with a higher prevalence among Black/African American smokers. Multivariable analyses, after adjusting for age, sex, assay batch, and number of cigarettes smoked per day, identified 14 AIMs near Phase I, II, and III pathway genes significantly associated with NNAL metabolizer phenotype, with African ancestry alleles conferring increased odds of poor metabolism. Functional annotation revealed that most significant AIMs overlapped regulatory regions, and the CYP3A5 rs776746 variant demonstrated structural disruption likely to impair enzymatic activity. Majority of participants had high African ancestry and were poor NNAL metabolizers, consistent with the observed association between African ancestry and poor NNAL metabolism. These findings highlight the biological basis for tobacco-related cancer disparities and underscore the importance of integrating genetic ancestry and metabolic phenotyping in risk assessment and personalized prevention strategies for tobacco-associated cancers.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Comparative life-cycle assessment of electrolyzer-integrated and air separation unit-based biomass conversion for net-negative emissions hydrogen production - Samira Rostom; Marc Duchesne; Robert Symonds; Robin W. Hughes (International Journal of Greenhouse Gas Control, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Decadal variability in mid-atmosphere temperature derived from continuous lidar observations - Pedro Da Costa Louro; Philippe Keckhut; Alain Hauchecorne; Robin Wing; Gerd Baumgarten; Michael Gerding; Thierry Leblanc; Bernd Kaifler; Natalie Kaifler; Wolfgang Steinbrecht; Ali Jalali; Robert J. Sica (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Cost-effective carbon-dioxide removal through water electrolysis and Oxy-BECCS integration - Samira Rostom; Robert Symonds; Robin W. Hughes; Scott Champagne (International Journal of Greenhouse Gas Control, 2025)

Coagulation temperature during cellulose regeneration from N-methylmorpholine-N-oxide (NMMO) influences the structure and ease of saccharification of lyocell byproducts - Sebastian España Orozco; Robin Hoheneder; Katharina Steiner; Solène Frécaut; Elisabeth Fitz; Robert H. Bischof (Carbohydrate Polymers, 2025)

Integrating the Maximum Entropy Production model and airborne imagery for understorey evapotranspiration mapping - Wenjie Liu; Okke Batelaan; David Bruce; Jingfeng Wang; Hugo Gutierrez; Hailong Wang; Robin Keegan-Treloar; Jianfeng Gou; Robert Keane; Jessica Thompson; Huade Guan (Journal of Hydrology, 2025)

A Comparison of the Biotechnological Potential of Marine and Terrestrial Species of Two Orders of Sordariomycete Fungi - Raquel Ledo Doval; Astrid Müller; Daren W. Brown; Derek Johnson; C. Alisha Quandt; Kerrie Barry; Alicia Clum; Hope Hundley; Kurt LaButti; Anna Lipzen; Stephen J. Mondo; Robin A. Ohm; et al. (Marine Biotechnology, 2025)

Optimizing automated photo identification for population assessments - Philip T. Patton; Krishna Pacifici; Robin W. Baird; Erin M. Oleson; Jason B. Allen; Erin Ashe; Aline Athayde; Charla J. Basran; Elsa Cabrera; John Calambokidis; Júlio Cardoso; Emma L. Carroll; et al. (Conservation Biology, 2025)
Several legal acts mandate that management agencies regularly assess biological populations. For species with distinct markings, these assessments can be conducted noninvasively via capture‐recapture and photographic identification (photo‐ID), which involves processing considerable quantities of photographic data. To ease this burden, agencies increasingly rely on automated identification (ID) algorithms. Identification algorithms present agencies with an opportunity—reducing the cost of population assessments—and a challenge—propagating misidentifications into abundance estimates at a large scale. We explored several strategies for generating capture histories with an ID algorithm, evaluating trade‐offs between labor costs and estimation error in a hypothetical population assessment. To that end, we conducted a simulation study informed by 39 photo‐ID datasets representing 24 cetacean species. We fed the results into a custom optimization tool to discern the optimal strategy for each dataset. Our strategies included choosing between truly and partially automated photo‐ID and, in the case of the latter, choosing the number of suggested matches to inspect. True automation was optimal for datasets for which the algorithm identified individuals well. As identification performance declined, the optimization recommended that users inspect more suggested matches from the ID algorithm, particularly for small datasets. False negatives (i.e., individual was resighted but erroneously marked as a first capture) strongly predicted estimation error. A 2% increase in the false negative rate translated to a 5% increase in the relative bias in abundance estimates. Our framework can be used to estimate expected error of the abundance estimate, project labor effort, and find the optimal strategy for a dataset and algorithm. We recommend estimating a strategy's false negative rate before implementing the strategy in a population assessment. Our framework provides organizations with insights into the conservation benefits and consequences of automation as conservation enters a new era of artificial intelligence for population assessments.

Psilocybin therapy for treatment resistant depression: prediction of clinical outcome by natural language processing - Robert F. Dougherty; Patrick Clarke; Merve Atli; Joanna Kuc; Danielle Schlosser; Boadie W. Dunlop; David J. Hellerstein; Scott T. Aaronson; Sidney Zisook; Allan H. Young; Robin Carhart-Harris; Guy M. Goodwin; et al. (Psychopharmacology, 2025)
Rationale Therapeutic administration of psychedelics has shown significant potential in historical accounts and recent clinical trials in the treatment of depression and other mood disorders. A recent randomized double-blind phase-IIb study demonstrated the safety and efficacy of COMP360, COMPASS Pathways’ proprietary synthetic formulation of psilocybin, in participants with treatment-resistant depression. Objective While the phase-IIb results are promising, the treatment works for a portion of the population and early prediction of outcome is a key objective as it would allow early identification of those likely to require alternative treatment. Methods Transcripts were made from audio recordings of the psychological support session between participant and therapist 1 day post COMP360 administration. A zero-shot machine learning classifier based on the BART large language model was used to compute two-dimensional sentiment (valence and arousal) for the participant and therapist from the transcript. These scores, combined with the Emotional Breakthrough Index (EBI) and treatment arm were used to predict treatment outcome as measured by MADRS scores. (Code and data are available at https://github.com/compasspathways/Sentiment2D .) Results Two multinomial logistic regression models were fit to predict responder status at week 3 and through week 12. Cross-validation of these models resulted in 85% and 88% accuracy and AUC values of 88% and 85%. Conclusions A machine learning algorithm using NLP and EBI accurately predicts long-term patient response, allowing rapid prognostication of personalized response to psilocybin treatment and insight into therapeutic model optimization. Further research is required to understand if language data from earlier stages in the therapeutic process hold similar predictive power.

Reproductive biology of invasive grass carp ( Ctenopharyngodon idella ) in two North American systems - Tammy M. Wilson; Matthew R. Acre; Fred Williams; Robin D. Calfee; Christine M. Mayer; Robert L. Mapes; Chris M. Kemp; Ryan T. Young; Michael E. Byrne (Journal of Fish Biology, 2025)
Grass carp ( Ctenopharyngodon idella ) are nonnative, herbivorous freshwater fish that represent an ecological threat in North American waters. However, data are limited on reproductive biology specific to wild populations in midwestern North America, despite recent concern for grass carp establishment within the Great Lakes. Basic information on reproductive traits could be useful to determine reproductive potential, inform future population modelling and provide information to aid control efforts. Our objectives were to evaluate grass carp age‐at‐maturity, spawning season timing, fecundity type, developmental timing and spawning strategy. Additionally, we evaluated the reliability of the gonadosomatic index (GSI) as a proxy for identifying mature grass carp and compared body condition across study areas. We sampled grass carp in portions of the Mississippi River watershed within the state of Missouri and within the Lake Erie basin. Based on gonad histological samples ( n = 274), grass carp are batch spawners with indeterminate fecundity and asynchronous ovarian developmental timing. This allows flexibility in their spawning, exemplified by a protracted spawning season in Lake Erie (April to November) in temperatures ranging from 12.3 to 27.3°C. Minimum observed age‐at‐maturity for females in Missouri and for both males and females in the Lake Erie population was age‐3 and age‐2 for males in Missouri. Accuracy of GSI as a measure of maturity during the spawning season was 89.7% and 87.5%, for females and males, respectively. Compared to Missouri, grass carp in Lake Erie had a significantly higher body condition, and females ready to spawn had significantly higher GSI values, suggesting that the grass carp in Lake Erie are healthier and more fecund relative to Missouri and, if left uncontrolled, potentially have a high probability of establishment within the Great Lakes. The results of this study will allow managers to identify the reproductive status of grass carp in the field and more accurately estimate populations and reproductive potential.

Spatial variation of future trends in Atlantic upwelling cells from two CMIP6 models - Raquel Flügel; Steven Herbette; Anne-Marie Treguier; Robin Waldman; Malcolm Roberts (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

A Multimedia Arsenic Exposure Assessment for the Hopi Tribe, AZ, USA - Adam C. Carl; Robert A. Canales; Jonathan E. Blohm; Lorencita Joshweseoma; Steven J. Hadeed; Jefferey L. Burgess; Robin B. Harris; Mary Kay O’Rourke (Exposure and Health, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Restoring genetic diversity to facilitate the implementation of the EU Nature Restoration Law - David O'Brien; Tsipe Aavik; Ancuta Fedorca; Martin C. Fischer; Robin Goffaux; Sean Hoban; Peter Hollingsworth; Christina Hvilsom; Robert Jehle; Belma Kalamujić Stroil; Francine Kershaw; Peter Klinga; et al. (Biological Conservation, 2025)

Predicting and assessing the impacts of COVID-19 disruption on marine science and sectors in Australia - Alistair J. Hobday; Vicki M. Walters; Robert L. Stephenson; Shane Baylis; Cindy Bessey; Fabio Boschetti; Catherine Bulman; Stephanie Contardo; Jeffrey M. Dambacher; Jemery Day; Natalie A. Dowling; Piers Dunstan; et al. (Reviews in Fish Biology and Fisheries, 2025)
By March 2020 coronavirus disease 2019 (COVID-19) was anticipated to present a major challenge to the work undertaken by scientists. This pandemic could be considered just one of the shocks that human society has had and will be likely to confront again in the future. As strategic thinking about the future can assist performance and planning of scientific research in the face of change, the pandemic presented an opportunity to evaluate the performance of marine researchers in prediction of future outcomes. In March 2020, two groups of researchers predicted outcomes for the Australian marine research sector, and then evaluated these predictions after 18 months. The self-assessed coping ability of a group experienced in ‘futures studies’ was not higher than the less-experienced group, suggesting that scientists in general may be well placed to cope with shocks. A range of changes to scientific endeavours (e.g., travel, fieldwork) and to marine sectors (e.g., fisheries, biodiversity) were predicted over the first 12–18 months of COVID-19 disruption. The predicted direction of change was generally correct (56%) or neutral (25%) for predictions related to the scientific endeavour, and correct (73%) or mixed (9%) for predictions related to sectors that are the focus of marine research. The success of this foresighting experiment suggests that the collective wisdom of scientists can be used by their organisations to consider the impact of shocks and disruptions and to better prepare for and cope with shocks. Graphical abstract Word cloud analysis of free text responses to questions about expected impact of COVID-19 on the activities associated with marine science

The Erosion of Threatened Southern Mountain Caribou Migration - Clayton T. Lamb; Robin Steenweg; Robert Serrouya; Dave Hervieux; R. Scott McNay; Douglas C. Heard; Bruce N. McLellan; Carolyn Shores; Eric Palm; Line Giguere; Jake Hubner; Jean Polfus; et al. (Global Change Biology, 2025)
Migration enables animals to access seasonally and spatially varying resources, resulting in greater abundance compared to analogous non‐migratory wildlife. Both Western science and Indigenous knowledge recognize the critical role of migration in sustaining wildlife; yet these movements are increasingly disrupted by human activity worldwide. Despite their importance, long‐term changes in migratory patterns for large mammals remain challenging to quantify. Therefore, to address this gap, we analyzed 35 years (1987–2022) of telemetry data for southern mountain caribou ( n = 2967 animal‐years), a threatened population that typically exhibits two main types of annual migration. The first type is a single horizontal migration between summer and winter ranges, while the second is a twice‐per‐year vertical migration between high and low elevations. We studied the extent and type of migration, changes through time, and determined if these changes correlated with landscape disturbance or shifts in weather. Our results show that caribou reduced their migratory duration (2–3 days/decade), distance (6–8 km/decade or 15%–25%) and elevation change (120–150 m/decade or 7%–23% for elevational migrants). The subpopulations of caribou adapted to extreme snow depths conducted a unique elevational migration twice a year, which is globally distinctive among ungulates. However, this elevational migration is diminishing in distance and elevation. The changes in elevational and horizontal migration correlated with increased human disturbance, especially of low‐elevation winter ranges. Changes in weather did not appear to be a major driver of the migratory declines. Declines in migratory behaviour occurred concomitantly with population declines and increases in disturbance, and these processes are likely intertwined. The rapid loss of these unique migrations is a significant conservation concern that could have irreversible consequences for the social transmission of fitness‐maximizing behaviors.

The interaction between values and self-identity on fairtrade consumption: The value-identity-behavior model - Sara Quach; Robin E. Roberts; Simon Dang; Alec Zuo; Park Thaichon (Appetite, 2025)

Multimodal creativity assessments following acute and sustained microdosing of lysergic acid diethylamide - Robin J. Murphy; Rachael L. Sumner; Kate Godfrey; Acima Mabidikama; Reece P. Roberts; Frederick Sundram; Suresh Muthukumaraswamy (Psychopharmacology, 2025)
Introduction Enhanced creativity is often cited as an effect of microdosing (taking repeated low doses of a psychedelic drug). There have been recent efforts to validate the reported effects of microdosing, however creativity remains a difficult construct to quantify. Objectives The current study aimed to assess microdosing’s effects on creativity using a multimodal battery of tests as part of a randomised controlled trial of microdosing lysergic acid diethylamide (LSD). Methods Eighty healthy adult males were given 10 µg doses of LSD or placebo every third day for six weeks (14 total doses). Creativity tasks were administered at a drug-free baseline session, at a first dosing session during the acute phase of the drug’s effects, and in a drug-free final session following the six-week microdosing regimen. Creativity tasks were the Alternate Uses Test (AUT), Remote Associates Task (RAT), Consensual Assessment Technique (CAT), and an Everyday Problem-Solving Questionnaire (EPSQ). Results No effect of drug by time was found on the AUT, RAT, CAT, or EPSQ. Baseline vocabulary skill had a significant effect on AUT and RAT scores. Conclusions Despite participants reporting feeling more creative on dose days, objective measurement found no acute or durable effects of the microdosing protocol on creativity. Possible explanations of these null findings are that laboratory testing conditions may negatively affect ability to detect naturalistic differences in creative performance, the tests available do not capture the facets of creativity that are anecdotally affected by microdosing, or that reported enhancements of creativity are placebo effects.

Corrections to: Assessment of Nannochloropsis gaditana growth and lipid accumulation with increased inorganic carbon delivery - Todd C. Pedersen; Robert D. Gardner; Robin Gerlach; Brent M. Peyton (Journal of Applied Phycology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

A Metapopulation Model to Assess Water Management Impacts on the Threatened Australian Lungfish, Neoceratodus forsteri - Charles R. Todd; Andrew J. McDougall; Scott M. C. Raymond; Robin Hale; Timothy R. Brown; John D. Koehn; Henry F. Wootton; Steven G. Brooks; Adrian M. Kitchingman; Tom Espinoza; Benjamin G. Fanson; Peter K. Kind; et al. (Fishes, 2025)
The Australian lungfish, Neoceratodus forsteri, is one of the world’s oldest vertebrate lineages, with a slow life-history and threatened status, requiring immediate conservation efforts. The main threats to lungfish populations are degradation and availability of key macrophyte habitats, water regulation and flow modification. As this long-lived species (at least 77 years) has delayed maturity (mature at 10 years), field monitoring alone will not be enough to inform the challenge of ensuring sustainable populations. A stochastic metapopulation model was developed for the Burnett River (Southeast Queensland, Australia), an important habitat for the lungfish that is a highly regulated system with extensive water infrastructure. The model consists of three interacting populations, where the ecology and biology of the species were translated into an 80-year-class population projection matrix for each population, each with post-development streamflow, habitat and movement rules. The model highlights the longer-term interaction between dams and stream flows on habitat availability and subsequent recruitment. Through a pre-development streamflow, we quantify the impact of high regulation and development on the lungfish population in the Burnett River: a minor decline in the upstream population (e.g., 9.8% decline), a large decline in the middle population (64.2% decline), virtually no change in the downstream population (e.g., 1.2% decline) and a moderate decline in the overall metapopulation (e.g., 22.3% decline). The loss of spawning and feeding habitat remains the main reason for population decline, with implications that the loss will lead to greater pressure on remaining downstream habitat due to combined flow and dam effects and, in turn, to extended periods of recovery of spawning habitat. Our modeling approach substantially advances conservation management of this species, as it can be adapted to suit other populations in other river systems and used to test sensitivity to recovery actions.

Trajectory priming through obstacle avoidance in motor imagery – does motor imagery comprise the spatial characteristics of movement? - James W. Roberts; Caroline J. Wakefield; Robin Owen (Experimental Brain Research, 2025)
Motor imagery and execution often indicate a similar trend in the temporal characteristics of movements. This finding supports the notion of functional equivalence, whereby imagery and execution use a common neural representation. However, there is comparatively limited evidence related to the spatial characteristics of movements; no doubt owing to the absence of an actual spatial trajectory during imagery. Therefore, we adapted the trajectory priming paradigm involving an obstacle, where the trajectory adopted in a trial ( n ) is directly contaminated by a previous trial ( n -1). If imagery accurately represents the spatial characteristics, then we would predict a similar priming effect as execution. Participants completed a series of trial blocks under different imagery/execution protocols, where the test trial ( n ) comprised execution alone, while the previous trial ( n -1) involved imagery or execution. Each block comprised pairs of trials with alternate or consistent presentations of a virtual obstacle (O) or no obstacle (N): N-N, N-O, O-N, O-O. For trial n -1 (imagery/execution), there was a more prolonged reaction and movement time for imagery compared execution. Most importantly for trial n (execution), there was an increase in early angular and peak deviation following an obstacle compared to no obstacle in trial n -1, but only when it was execution and not imagery. These findings suggest imagery holds a limited representation of the spatial characteristics, while functional equivalence may be limited to the temporal characteristics.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

The RapidMapper: State-of-the-art in mobile proximal soil sensing based on a novel multi-sensor platform - Hamed Tavakoli; José Correa; Sebastian Vogel; Marcel Oertel; Marc Zimne; Michael Heisig; Anatolij Harder; Robert Wruck; Stefan Pätzold; Matthias Leenen; Robin Gebbers (Computers and Electronics in Agriculture, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

The influence of habitat alteration is widespread, but the impact of climate cannot continue to be discounted - Melanie Dickie; Robert Serrouya; Marcus Becker; Craig DeMars; Michael J. Noonan; Robin Steenweg; Stan Boutin; Adam T. Ford (Global Change Biology, 2024)

ITPK1 is an InsP6/ADP phosphotransferase that controls phosphate signaling in Arabidopsis - Esther Riemer; Danye Qiu; Debabrata Laha; Robert K. Harmel; Philipp Gaugler; Verena Gaugler; Michael Frei; Mohammad-Reza Hajirezaei; Nargis Parvin Laha; Lukas Krusenbaum; Robin Schneider; Adolfo Saiardi; et al. (Molecular Plant, 2024)

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Establishment of the deuterium oxide dilution method as a new possibility for determining the transendothelial water permeability - Hannes Müller; Janina Hahn; Angelina Gierke; Robert Stark; Cornelia Brunner; Thomas K. Hoffmann; Jens Greve; Oliver Wittekindt; Robin Lochbaum (Pflügers Archiv - European Journal of Physiology, 2024)
Increase in transendothelial water permeability is an essential etiological factor in a variety of diseases like edema and shock. Despite the high clinical relevance, there has been no precise method to detect transendothelial water flow until now. The deuterium oxide (D 2 O) dilution method, already established for measuring transepithelial water transport, was used to precisely determine the transendothelial water permeability. It detected appropriate transendothelial water flow induced by different hydrostatic forces. This was shown in four different endothelial cell types. The general experimental setup was verified by gravimetry and absorbance spectroscopy. Determination of transendothelial electrical resistance (TEER) and immunocytochemical staining for proteins of the cell-cell contacts were performed to ensure that no damage to the endothelium occurred because of the measurements. Furthermore, endothelial barrier function was modulated. Measurement of transendothelial water flux was verified by measuring the TEER, the apparent permeability coefficient and the electrical capacity. The barrier-promoting substances cyclic adenosine monophosphate and iloprost reduced TEER and electrical capacity and increased permeability. This was accompanied by a reduced transendothelial water flux. In contrast, the barrier-damaging substances thrombin, histamine and bradykinin reduced TEER and electrical capacity, but increased permeability. Here, an increased water flow was shown. This newly established in vitro method for direct measurement of transendothelial water permeability was verified as a highly precise technique in various assays. The use of patient-specific endothelial cells enables individualized precision medicine in the context of basic edema research, for example regarding the development of barrier-protective pharmaceuticals.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Habitat alteration or climate: What drives the densities of an invading ungulate? - Melanie Dickie; Robert Serrouya; Marcus Becker; Craig DeMars; Michael J. Noonan; Robin Steenweg; Stan Boutin; Adam T. Ford (Global Change Biology, 2024)
Anthropogenic habitat alteration and climate change are two well‐known contributors to biodiversity loss through changes to species distribution and abundance; yet, disentangling the effects of these two factors is often hindered by their inherent confound across both space and time. We leveraged a contrast in habitat alteration associated with the jurisdictional boundary between two Canadian provinces to evaluate the relative effects of spatial variation in habitat alteration and climate on white‐tailed deer ( Odocoileus virginianus ) densities. White‐tailed deer are an invading ungulate across much of North America, whose expansion into Canada's boreal forest is implicated in the decline of boreal caribou ( Rangifer tarandus caribou ), a species listed as Threatened in Canada. We estimated white‐tailed deer densities using 300 remote cameras across 12 replicated 50 km 2 landscapes over 5 years. White‐tailed deer densities were significantly lower in areas where winter severity was higher. For example, predicted deer densities declined from 1.83 to 0.35 deer/km 2 when winter severity increased from the lowest value to the median value. There was a tendency for densities to increase with increasing habitat alteration; however, the magnitude of this effect was approximately half that of climate. Our findings suggest that climate is the primary driver of white‐tailed deer populations; however, understanding the mechanisms underpinning this relationship requires further study of over‐winter survival and fecundity. Long‐term monitoring at the invasion front is needed to evaluate the drivers of abundance over time, particularly given the unpredictability of climate change and increasing prevalence of extreme weather events.

Overprinting orogenic events, ductile extrusion and strain partitioning during Caledonian transpression, NW Mainland Shetland - Timothy B. Armitage; Robert E. Holdsworth; Robin A. Strachan; Edward D. Dempsey; Richard J. Walker; Diana T. Alvarez-Ruiz; Geoffrey E. Lloyd (Journal of Structural Geology, 2024)

Reasons to Be Skeptical about Sentience and Pain in Fishes and Aquatic Invertebrates - Benjamin K. Diggles; Robert Arlinghaus; Howard I. Browman; Steven J. Cooke; Robin L. Cooper; Ian G. Cowx; Charles D. Derby; Stuart W. Derbyshire; Paul JB Hart; Brian Jones; Alexander O. Kasumyan; Brian Key; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Genome-scale phylogeny and comparative genomics of the fungal order Sordariales - Noah Hensen; Lucas Bonometti; Ivar Westerberg; Ioana Onut Brännström; Sonia Guillou; Sandrine Cros-Aarteil; Sara Calhoun; Sajeet Haridas; Alan Kuo; Stephen Mondo; Jasmyn Pangilinan; Robert Riley; et al. (Molecular Phylogenetics and Evolution, 2023)

Are transport networks in low-income countries prepared for climate change? Barriers to preparing for climate change in Africa and South Asia - Sarah Greenham; Robin Workman; Kevin McPherson; Emma Ferranti; Rachel Fisher; Stephen Mills; Roger Street; John Dora; Andrew Quinn; Clive Roberts (Mitigation and Adaptation Strategies for Global Change, 2023)
Climate change, through extreme weather events and slow onset climatic changes, disrupts the operation of transport networks, and those in low-income countries (LICs) across Africa and South Asia are particularly vulnerable to climate change. This paper explores the barriers that LICs face across Africa and South Asia regarding preparedness of transport infrastructure to climate change, with the intent of addressing the knowledge gaps and consequential needs of LICs to support the delivery of more climate-resilient transport. Literature on climate change adaptation and transport resilience among LICs is reviewed to identify the broad challenges and barriers regarding climate change adaptation. Semi-structured interviews with 13 transport stakeholders across Africa and South Asia were also conducted to understand the challenges specific to the transport sector in the regions. Several barriers were identified, including a lack of data and knowledge on climate change impacts, design and prioritisation of remedial actions, budgeting and planning for climate change, and identifying and engaging with stakeholders. Findings from this paper and the wider research project it comprises inform policy guidance that calls for greater national and international coordination to develop practical, relevant and usable data, tools, advice and support for some of the most at-risk transport networks to climate change in the world.

Quantification of Uncertainties of Radiative Transfer Calculation in Urban Canopy Models - Robert Schoetter; Cyril Caliot; Tin-Yuet Chung; Robin J. Hogan; Valéry Masson (Boundary-Layer Meteorology, 2023)

Toward decentralized wastewater treatment: A flow-through module using microtubular gas diffusion electrodes for micropollutants removal - Mojtaba Mohseni; Daniel Felder; Korcan Percin; Maximilian Thönes; Matthias Gassenmeier; Robin Kupec; Claudia Weidlich; John Linkhorst; Robert G. Keller; Matthias Wessling (Journal of Hazardous Materials, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Survey Outcome on Immunogenicity Risk Assessment Tools for Biotherapeutics: an Insight into Consensus on Methods, Application, and Utility in Drug Development - Jochem Gokemeijer; Yi Wen; Vibha Jawa; Shibani Mitra-Kaushik; Shan Chung; Alan Goggins; Seema Kumar; Kasper Lamberth; Karen Liao; Jennie Lill; Qui Phung; Robin Walsh; et al. (The AAPS Journal, 2023)

Intervention-forward adaptive management in the face of extinction - Melanie Dickie; Adam T. Ford; Robin Steenweg; Robert Serrouya (Trends in Ecology & Evolution, 2023)

Biologically inspired robotic perception-action for soft fruit harvesting in vertical growing environments - Fuli Wang; Rodolfo Cuan Urquizo; Penelope Roberts; Vishwanathan Mohan; Chris Newenham; Andrey Ivanov; Robin Dowling (Precision Agriculture, 2023)
Multiple interlinked factors like demographics, migration patterns, and economics are presently leading to the critical shortage of labour available for low-skilled, physically demanding tasks like soft fruit harvesting. This paper presents a biomimetic robotic solution covering the full ‘Perception-Action’ loop targeting harvesting of strawberries in a state-of-the-art vertical growing environment. The novelty emerges from both dealing with crop/environment variance as well as configuring the robot action system to deal with a range of runtime task constraints. Unlike the commonly used deep neural networks, the proposed perception system uses conditional Generative Adversarial Networks to identify the ripe fruit using synthetic data. The network can effectively train the synthetic data using the image-to-image translation concept, thereby avoiding the tedious work of collecting and labelling the real dataset. Once the harvest-ready fruit is localised using point cloud data generated by a stereo camera, our platform’s action system can coordinate the arm to reach/cut the stem using the Passive Motion Paradigm framework inspired by studies on neural control of movement in the brain. Results from field trials for strawberry detection, reaching/cutting the stem of the fruit, and extension to analysing complex canopy structures/bimanual coordination (searching/picking) are presented. While this article focuses on strawberry harvesting, ongoing research towards adaptation of the architecture to other crops such as tomatoes and sweet peppers is briefly described.

Emerging themes and future directions in watershed resilience research - Fernando Miralles-Wilhelm; John H. Matthews; Nathan Karres; Robin Abell; James Dalton; Shi-Teng Kang; Junguo Liu; Romain Maendly; Nathanial Matthews; Robert McDonald; Raúl Muñoz-Castillo; Boris F. Ochoa-Tocachi; et al. (Water Security, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Peering down the sink: A review of isoprene metabolism by bacteria - Robin A. Dawson; Andrew T. Crombie; Robert S. Jansen; Thomas J. Smith; Tim Nichol; Colin Murrell (Environmental Microbiology, 2023)
Isoprene (2‐methyl‐1,3‐butadiene) is emitted to the atmosphere each year in sufficient quantities to rival methane (>500 Tg C yr −1 ), primarily due to emission by trees and other plants. Chemical reactions of isoprene with other atmospheric compounds, such as hydroxyl radicals and inorganic nitrogen species (NO x ), have implications for global warming and local air quality, respectively. For many years, it has been estimated that soil‐dwelling bacteria consume a significant amount of isoprene (~20 Tg C yr −1 ), but the mechanisms underlying the biological sink for isoprene have been poorly understood. Studies have indicated or confirmed the ability of diverse bacterial genera to degrade isoprene, whether by the canonical iso ‐type isoprene degradation pathway or through other less well‐characterized mechanisms. Here, we review current knowledge of isoprene metabolism and highlight key areas for further research. In particular, examples of isoprene‐degraders that do not utilize the isoprene monooxygenase have been identified in recent years. This has fascinating implications both for the mechanism of isoprene uptake by bacteria, and also for the ecology of isoprene‐degraders in the environments.

Modelling of fracture intensity increase due to interacting blast waves in three-dimensional granitic rocks - Robert Bird; Adriana Paluszny; Robin N. Thomas; Robert W. Zimmerman (International Journal of Rock Mechanics and Mining Sciences, 2023)

Corrigendum: Associations between cyanobacteria and indices of secondary production in the western basin of Lake Erie - James H. Larson; Mary Anne Evans; Robert J. Kennedy; Sean W. Bailey; Keith A. Loftin; Zachary R. Laughrey; Robin A. Femmer; Jeff S. Schaeffer; William B. Richardson; Timothy T. Wynne; J. C. Nelson; Joseph W. Duris (Limnology and Oceanography, 2022)
In the last year, we became aware that data used in our above‐referenced manuscript from 2018 published in Limnology and Oceanography contained significant errors. In the 2018 manuscript, we found that indices of secondary production were negatively correlated to indices of cyanobacterial abundance and toxicity. Unfortunately, one of our indices of cyanobacterial abundance (biovolume) and our measurement of toxicity (microcystin concentration) were inaccurate in the data we used in the 2018 manuscript. Upon discovering these errors, we immediately began correcting the repositories where these data were available. Having corrected those data repositories, we are now reporting on the re‐analysis of the data using the methods previously described in the 2018 manuscript. Although the relationships are slightly different, our interpretation is that the conclusions of the 2018 manuscript are still valid using the corrected data. The data errors we experienced were traced to a spreadsheet that was used to share data among the research team, which had errors caused by mistakes in copy‐pasting formulas instead of data and ‘inadvertent’ edits that were saved by the spreadsheet's auto‐save function. We apologize to the scientific community for these errors.

Worldwide phylogeography of rough‐toothed dolphins ( Steno bredanensis ) provides evidence for subspecies delimitation - G. Renee Albertson; Alana Alexander; Frederick I. Archer; Susana Caballero; Karen K. Martien; Lenaïg G. Hemery; Robin W. Baird; Marc Oremus; M. Michael Poole; Deborah A. Duffield; Robert L. Brownell; Dan Kerem; et al. (Marine Mammal Science, 2022)
Rough‐toothed dolphins ( Steno bredanensis ) have a global tropical and subtropical distribution with oceanic, neritic, and island‐associated populations. To inform conservation and management for this species, we used sequences from the mtDNA control region ( n = 360), mitogenomes ( n = 19), and six nuclear introns ( n = 35) to provide multiple lines of evidence to critically evaluate the potential taxonomic status of rough‐toothed dolphins. Using samples from the Pacific, Indian, and Atlantic Oceans, we examined the null hypothesis that rough‐toothed dolphins are one panmictic species and the alternate hypothesis of oceanic subspecies. Phylogenetic analyses of mitogenomes revealed a private Atlantic clade sister to a larger cosmopolitan clade including individuals from all tropical and subtropical oceans. We dated the split between the Atlantic clade and the cosmopolitan clade to 890,000 years ago. We determined that Atlantic rough‐toothed dolphins could be correctly diagnosed with 98% accuracy with the mtDNA control region and calculated the net nucleotide divergence as 0.02. Population level analyses revealed significant genetic differentiation using mtDNA among most regions, while significant differentiation using nuclear markers occurred only between the Atlantic and the Indian/Pacific regions. Therefore, the oceanic divergence and diagnosability of rough‐toothed dolphins in the Atlantic and the Indian/Pacific Oceans meet proposed criteria for recognition as two subspecies.

Basin-wide estimates of loggerhead turtle abundance in the Mediterranean Sea derived from line transect surveys - Andrew DiMatteo; Ana Cañadas; Jason Roberts; Laura Sparks; Simone Panigada; Olivier Boisseau; Anna Moscrop; Caterina Maria Fortuna; Giancarlo Lauriano; Draško Holcer; Hélène Peltier; Vincent Ridoux; et al. (Frontiers in Marine Science, 2022)
Loggerhead turtles are a globally vulnerable species of marine turtle. Broad-scale patterns of distribution and abundance can provide regional managers a tool to effectively conserve and manage this species at basin and sub-basin scales. In this study, combined aerial and shipboard line transect survey data collected between 2003 and 2018 were used to estimate distribution and abundance throughout the Mediterranean Sea. Approximately 230,000 linear kilometers of survey effort, from seven different surveying organizations were incorporated into a generalized additive model to relate loggerhead density on survey segments to environmental conditions. Two spatial density models estimating loggerhead density, abundance, and distribution were generated – one a long-term annual average covering 2003-2018 and another covering the summer of 2018, when a basin-wide aerial survey, the Agreement on the Conservation of Cetaceans of the Black Sea, Mediterranean Sea and Contiguous Atlantic Area Survey Initiative, was performed. Both models were adjusted for availability bias using dive data from loggerhead turtles tagged with time depth recorders. Mean abundance for the long-term average model was estimated as 1,201,845 (CV=0.22). The summer 2018 abundance estimate was 789,244 turtles and covered a smaller area than the long-term average. These estimates represent the first basin-wide estimates of abundance for loggerhead turtles in the Mediterranean not based on demographic models. Both models predicted similar distributions, with higher abundance predicted in the northern Adriatic Sea, central Mediterranean basin, Tyrrhenian Sea, and south of the Balearic Islands. Lower densities were predicted in the eastern Mediterranean Sea and the Aegean Sea. The highest density areas generally did not coincide with previously established adult loggerhead turtle foraging areas, which are typically neritic, indicating the models are predominantly predicting oceanic distributions, where most of the survey effort occurred. Juvenile loggerhead turtles are predominantly oceanic and comprise most of the population, but care must be taken when using these models as they may not accurately predict distribution of neritic foraging areas, where subadult and adult loggerheads can often be found. Despite this limitation, these models represent a major step forward for conservation planning and understanding basin-wide distribution and abundance patterns of this species.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Exploring ecosystem‐based management in the North Atlantic - Mark Dickey‐Collas; Jason S. Link; Paul Snelgrove; J. Murray Roberts; M. Robin Anderson; Ellen Kenchington; Alida Bundy; Margaret M. (Peg) Brady; Rebecca L. Shuford; Howard Townsend; Anna Rindorf; Murray A. Rudd; et al. (Journal of Fish Biology, 2022)
The United States, the EU and Canada established a trilateral working group on the ecosystem approach to ocean health and stressors under the Atlantic Ocean Research Alliance. Recognizing the Atlantic Ocean as a shared resource and responsibility, the working group sought to advance understanding of the Atlantic Ocean and its dynamic systems to improve ocean health, enhance ocean stewardship and promote the sustainable use and management of its resources. This included consideration of multiple ocean‐use sectors such as fishing, shipping, tourism and offshore energy. The working group met for 4 years and worked through eight steps that covered the development of common language as a basis for collaboration, challenges of stakeholder engagement, review of the governance mandates, exploring the links between sectors and ecosystems effects, identifying gaps in knowledge and uptake of science, identification of tools for ecosystem‐based management, customary best practice for tool development and communication of key research priorities. The key findings were that ecosystem‐based management enables new benefits and opportunities, and that we need to make the business case. Further findings were that adequate mandates and effective tools exist for ecosystem‐based management, and that ecosystem‐based management urgently requires integration of human dimensions, so we must diversify the conversation. In addition, it was found that stakeholders do not see their stake in ecosystem‐based management, so greater engagement with stakeholders and targeting of ocean literacy is required and a sustainable future requires a sustained investment in ecosystem‐based management, so long‐term commitment is key.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Compound urban crises - Linda Westman; James Patterson; Rachel Macrorie; Christopher J. Orr; Catherine M. Ashcraft; Vanesa Castán Broto; Dana Dolan; Mukesh Gupta; Jeroen van der Heijden; Thomas Hickmann; Robert Hobbins; Marielle Papin; et al. (Ambio, 2022)
The crises that cities face—such as climate change, pandemics, economic downturn, and racism—are tightly interlinked and cannot be addressed in isolation. This paper addresses compound urban crises as a unique type of problem, in which discrete solutions that tackle each crisis independently are insufficient. Few scholarly debates address compound urban crises and there is, to date, a lack of interdisciplinary insights to inform urban governance responses. Combining ideas from complex adaptive systems and critical urban studies, we develop a set of boundary concepts (unsettlement, unevenness, and unbounding) to understand the complexities of compound urban crises from an interdisciplinary perspective. We employ these concepts to set a research agenda on compound urban crises, highlighting multiple interconnections between urban politics and global dynamics. We conclude by suggesting how these entry points provide a theoretical anchor to develop practical insights to inform and reform urban governance.

Climate variability and aridity modulate the role of leaf shelters for arthropods: A global experiment - Gustavo Q. Romero; Thiago Gonçalves‐Souza; Tomas Roslin; Robert J. Marquis; Nicholas A.C. Marino; Vojtech Novotny; Tatiana Cornelissen; Jerome Orivel; Shen Sui; Gustavo Aires; Reuber Antoniazzi; Wesley Dáttilo; et al. (Global Change Biology, 2022)
Current climate change is disrupting biotic interactions and eroding biodiversity worldwide. However, species sensitive to aridity, high temperatures, and climate variability might find shelter in microclimatic refuges, such as leaf rolls built by arthropods. To explore how the importance of leaf shelters for terrestrial arthropods changes with latitude, elevation, and climate, we conducted a distributed experiment comparing arthropods in leaf rolls versus control leaves across 52 sites along an 11,790 km latitudinal gradient. We then probed the impact of short‐ versus long‐term climatic impacts on roll use, by comparing the relative impact of conditions during the experiment versus average, baseline conditions at the site. Leaf shelters supported larger organisms and higher arthropod biomass and species diversity than non‐rolled control leaves. However, the magnitude of the leaf rolls’ effect differed between long‐ and short‐term climate conditions, metrics (species richness, biomass, and body size), and trophic groups (predators vs. herbivores). The effect of leaf rolls on predator richness was influenced only by baseline climate, increasing in magnitude in regions experiencing increased long‐term aridity, regardless of latitude, elevation, and weather during the experiment. This suggests that shelter use by predators may be innate, and thus, driven by natural selection. In contrast, the effect of leaf rolls on predator biomass and predator body size decreased with increasing temperature, and increased with increasing precipitation, respectively, during the experiment. The magnitude of shelter usage by herbivores increased with the abundance of predators and decreased with increasing temperature during the experiment. Taken together, these results highlight that leaf roll use may have both proximal and ultimate causes. Projected increases in climate variability and aridity are, therefore, likely to increase the importance of biotic refugia in mitigating the effects of climate change on species persistence.

Correction to: Associations Between Two Measures of Trunk Muscular Endurance Among Male Law Enforcement Officers - J. Jay Dawes; Cody A. Stahl; Robert G. Lockie; Jan E. Redmond; Charlie Kornhauser; Ryan J. Holmes; Robin M. Orr (Journal of Science in Sport and Exercise, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

The natural history of OTOF-related auditory neuropathy spectrum disorders: a multicenter study - Ryan K. Thorpe; Hela Azaiez; Peina Wu; Qiuju Wang; Lei Xu; Pu Dai; Tao Yang; G. Bradley Schaefer; B. Robert Peters; Kenny H. Chan; Krista S. Schatz; Joann Bodurtha; et al. (Human Genetics, 2022)

Subtle structures with not‐so‐subtle functions: A data set of arthropod constructs and their host plants - Cássio Cardoso Pereira; Samuel Novais; Milton Barbosa; Daniel Negreiros; Thiago Gonçalves‐Souza; Tomas Roslin; Robert Marquis; Nicholas Marino; Vojtech Novotny; Jerome Orivel; Shen Sui; Gustavo Aires; et al. (Ecology, 2022)
The construction of shelters on plants by arthropods might influence other organisms via changes in colonization, community richness, species composition, and functionality. Arthropods, including beetles, caterpillars, sawflies, spiders, and wasps often interact with host plants via the construction of shelters, building a variety of structures such as leaf ties, tents, rolls, and bags; leaf and stem galls, and hollowed out stems. Such constructs might have both an adaptive value in terms of protection (i.e., serve as shelters) but may also exert a strong influence on terrestrial community diversity in the engineered and neighboring hosts via colonization by secondary occupants. Although different traits of the host plant (e.g., physical, chemical, and architectural features) may affect the potential for ecosystem engineering by insects, such effects have been, to a certain degree, overlooked. Further analyses of how plant traits affect the occurrence of shelters may therefore enrich our understanding of the organizing principles of plant‐based communities. This data set includes more than 1000 unique records of ecosystem engineering by arthropods, in the form of structures built on plants. All records have been published in the literature, and span both natural structures (91% of the records) and structures artificially created by researchers (9% of the records). The data were gathered between 1932 and 2021, across more than 50 countries and several ecosystems, ranging from polar to tropical zones. In addition to data on host plants and engineers, we aggregated data on the type of constructs and the identity of inquilines using these structures. This data set highlights the importance of these subtle structures for the organization of terrestrial arthropod communities, enabling hypotheses testing in ecological studies addressing ecosystem engineering and facilitation mediated by constructs. There are no copyright restrictions and please cite this paper when using the data in publications.

Global drivers of avian haemosporidian infections vary across zoogeographical regions - Alan Fecchio; Nicholas J. Clark; Jeffrey A. Bell; Heather R. Skeen; Holly L. Lutz; Gabriel M. De La Torre; Jefferson A. Vaughan; Vasyl V. Tkach; Fabio Schunck; Francisco C. Ferreira; Érika M. Braga; Camile Lugarini; et al. (Global Ecology and Biogeography, 2021)
Aim Macroecological analyses provide valuable insights into factors that influence how parasites are distributed across space and among hosts. Amid large uncertainties that arise when generalizing from local and regional findings, hierarchical approaches applied to global datasets are required to determine whether drivers of parasite infection patterns vary across scales. We assessed global patterns of haemosporidian infections across a broad diversity of avian host clades and zoogeographical realms to depict hotspots of prevalence and to identify possible underlying drivers. Location Global. Time period 1994–2019. Major taxa studied Avian haemosporidian parasites (genera Plasmodium , Haemoproteus , Leucocytozoon and Parahaemoproteus ). Methods We amalgamated infection data from 53,669 individual birds representing 2,445 species world‐wide. Spatio‐phylogenetic hierarchical Bayesian models were built to disentangle potential landscape, climatic and biotic drivers of infection probability while accounting for spatial context and avian host phylogenetic relationships. Results Idiosyncratic responses of the three most common haemosporidian genera to climate, habitat, host relatedness and host ecological traits indicated marked variation in host infection rates from local to global scales. Notably, host ecological drivers, such as migration distance for Plasmodium and Parahaemoproteus , exhibited predominantly varying or even opposite effects on infection rates across regions, whereas climatic effects on infection rates were more consistent across realms. Moreover, infections in some low‐prevalence realms were disproportionately concentrated in a few local hotspots, suggesting that regional‐scale variation in habitat and microclimate might influence transmission, in addition to global drivers. Main conclusions Our hierarchical global analysis supports regional‐scale findings showing the synergistic effects of landscape, climate and host ecological traits on parasite transmission for a cosmopolitan and diverse group of avian parasites. Our results underscore the need to account for such interactions, in addition to possible variation in drivers across regions, to produce the robust inference required to predict changes in infection risk under future scenarios.

Social comfort zones for transformative conservation decisions in a changing climate - Shannon Hagerman; Terre Satterfield; Sara Nawaz; Guillaume Peterson St‐Laurent; Robert Kozak; Robin Gregory (Conservation Biology, 2021)
Novel management interventions intended to mitigate the impacts of climate change on biodiversity are increasingly being considered by scientists and practitioners. However, resistance to more transformative interventions remains common across both specialist and lay communities and is generally assumed to be strongly entrenched. We used a decision‐pathways survey of the public in Canada and the United States ( n = 1490) to test two propositions relating to climate‐motivated interventions for conservation: most public groups are uncomfortable with interventionist options for conserving biodiversity and given the strong values basis for preferences regarding biodiversity and natural systems more broadly, people are unlikely to change their minds. Our pathways design tested and retested levels of comfort with interventions for forest ecosystems at three different points in the survey. Comfort was reexamined given different nudges (including new information from trusted experts) and in reference to a particular species (bristlecone pine [ Pinus longaeva ]). In contrast with expectations of public unease, baseline levels of public comfort with climate interventions in forests was moderately high (46% comfortable) and increased further when respondents were given new information and the opportunity to change their choice after consideration of a particular species. People who were initially comfortable with interventions tended to remain so (79%), whereas 42% of those who were initially uncomfortable and 40% of those who were uncertain shifted to comfortable by the end of the survey. In short and across questions, comfort levels with interventions were high, and where discomfort or uncertainty existed, such positions did not appear to be strongly held. We argue that a new decision logic, one based on anthropogenic responsibility, is beginning to replace a default reluctance to intervene with nature.

Associations Between Two Measures of Trunk Muscular Endurance Among Male Law Enforcement Officers - J. Jay Dawes; Cody A. Stahl; Robert G. Lockie; Jan E. Redmond; Charles L. Kornhauser; Ryan J. Holmes; Robin M. Orr (Journal of Science in Sport and Exercise, 2021)

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

Female song in the Cyprus Wheatear Oenanthe cypriaca - Robert Patchett; Alexander N. G. Kirschel; Joanna Robins King; Patrick Styles; Will Cresswell (Journal of Ornithology, 2021)
Female song is widespread across bird species yet rarely reported. Here, we report the first observations and description of female song in the Cyprus Wheatear Oenanthe cypriaca and compare it to male song through the breeding season. Twenty-five percent of colour-ringed females were observed singing at least once, predominantly in April, compared to 71% of males that continued singing through the breeding period. We suggest that female song may have multiple functions in this species, but it may be especially important in territorial defence and mate acquisition.

Relationship Between Metabolic Fitness and Performance in Police Occupational Tasks - Elisa F. D. Canetti; J. Jay Dawes; Phoebe H. Drysdale; Robert Lockie; Charlie Kornhauser; Ryan Holmes; Ben Schram; Robin M. Orr (Journal of Science in Sport and Exercise, 2021)
Purpose To determine the relationship between metabolic fitness test scores and performance in police occupational tasks. Methods Retrospective data from 106 law enforcement officers who completed two metabolic fitness assessments [anaerobic: a 20-m (10-m and 20-m splits) sprint, aerobic: 20 m Multi-Stage Fitness Test (20 m-MSFT)] and three routine occupational tasks [1.22 m Fence jump (FJ), 8.5 m Victim Drag (VD with 102.3 kg) and “Get-up” (GU)] were collected. A Person’s correlation coefficient and a standard multiple regression were used to assess the relationship between and predictive ability of, respectively, the fitness tests scores and performance on occupational tasks. Results There was a significant positive correlation between the 10-m sprint scores and FJ ( r = 0.524, P < 0.001), VD ( r = 0.528, P < 0.001) and GU ( r = 0.486, P < 0.001). Similarly, the 20-m sprint scores were significantly and moderately correlated with FJ ( r = 0.573, P < 0.001), VD ( r = 0.603, P < 0.001) and GU ( r = 0.533, P < 0.001). These anaerobic tests’ scores predicted approximately 40% of the performance in the occupational tasks analysed. The MSFT fitness assessment had a small, albeit significant negative correlation with the three tasks: FJ ( r = − 0.360, P < 0.001), VD ( r = − 0.266, P = 0.012) and GU ( r = − 0.375, P < 0.001). Conclusion High levels of metabolic fitness correlated with faster performance in police officer occupational tasks, particularly ones of an anaerobic nature (i.e. the maximal sprint tests). In addition to typical aerobic fitness conditioning, anaerobic fitness conditioning could be vital for optimal performance in physically demanding tasks required of police officer.

Under pressure: conservation choices and the threat of species extinction - Robin Gregory; Robert Kozak; Guillaume Peterson St-Laurent; Sara Nawaz; Terre Satterfield; Shannon Hagerman (Climatic Change, 2021)

Cycling in degradation of organic polymers and uptake of nutrients by a litter‐degrading fungus - Aurin M. Vos; Robert‐Jan Bleichrodt; Koen C. Herman; Robin A. Ohm; Karin Scholtmeijer; Heike Schmitt; Luis G. Lugones; Han A. B. Wösten (Environmental Microbiology, 2021)
Summary Wood and litter degrading fungi are the main decomposers of lignocellulose and thus play a key role in carbon cycling in nature. Here, we provide evidence for a novel lignocellulose degradation strategy employed by the litter degrading fungus Agaricus bisporus (known as the white button mushroom). Fusion of hyphae allows this fungus to synchronize the activity of its mycelium over large distances (50 cm). The synchronized activity has a 13‐h interval that increases to 20 h before becoming irregular and it is associated with a 3.5‐fold increase in respiration, while compost temperature increases up to 2°C. Transcriptomic analysis of this burst‐like phenomenon supports a cyclic degradation of lignin, deconstruction of (hemi‐) cellulose and microbial cell wall polymers, and uptake of degradation products during vegetative growth of A. bisporus . Cycling in expression of the ligninolytic system, of enzymes involved in saccharification, and of proteins involved in nutrient uptake is proposed to provide an efficient way for degradation of substrates such as litter.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Assessing the sublethal impacts of anthropogenic stressors on fish: An energy‐budget approach - Joseph W. Watson; Kieran Hyder; Robin Boyd; Robert Thorpe; Marc Simon Weltersbach; Keno Ferter; Steven J. Cooke; Shovonlal Roy; Richard M. Sibly (Fish and Fisheries, 2020)
Fish are increasingly exposed to anthropogenic stressors from human developments and activities such as agriculture, urbanization, pollution and fishing. Lethal impacts of these stressors have been studied but the potential sublethal impacts, such as behavioural changes or reduced growth and reproduction, have often been overlooked. Unlike mortality, sublethal impacts are broad and difficult to quantify experimentally. As a result, sublethal impacts are often ignored in regulatory frameworks and management decisions. Building on established fish bioenergetic models, we present a general method for using the population consequences of disturbance framework to investigate how stressors influence ecologically relevant life processes of fish. We partition impact into the initial energetic cost of attempts to escape from the stressor, followed by the energetic impacts of any injury or behavioural change, and their consequent effects on life processes. As a case study, we assess the sublethal effects of catch and release angling for the European sea bass ( Dicentrachus labrax , Moronidae ), a popular target species for recreational fishers. The energy budget model described is not intended to replace existing experimental approaches but does provide a simple way to account for sublethal impacts in assessment of the impact of recreational fisheries and aid development of robust management approaches. There is potential to apply our energy budget approach to investigate a broad range of stressors and cumulative impacts for many fish species while also using individual‐based models to estimate population‐level impacts.

Potential Consequences of Climate and Management Scenarios for the Northeast Atlantic Mackerel Fishery - Robin Boyd; Robert Thorpe; Kieran Hyder; Shovonlal Roy; Nicola Walker; Richard Sibly (Frontiers in Marine Science, 2020)

Stabilization of myeloid-derived HIFs promotes vascular regeneration in retinal ischemia - Pilar Villacampa; Sidath E. Liyanage; Izabela P. Klaska; Enrico Cristante; Katja E. Menger; Robert D. Sampson; Maeve Barlow; Laura Abelleira-Hervas; Yanai Duran; Alexander J. Smith; Robin R. Ali; Ulrich F. O. Luhmann; et al. (Angiogenesis, 2020)
The retinal vasculature is tightly organized in a structure that provides for the high metabolic demand of neurons while minimizing interference with incident light. The adverse impact of retinal vascular insufficiency is mitigated by adaptive vascular regeneration but exacerbated by pathological neovascularization. Aberrant growth of neovessels in the retina is responsible for impairment of sight in common blinding disorders including retinopathy of prematurity, proliferative diabetic retinopathy, and age-related macular degeneration. Myeloid cells are key players in this process, with diverse roles that can either promote or protect against ocular neovascularization. We have previously demonstrated that myeloid-derived VEGF, HIF1, and HIF2 are not essential for pathological retinal neovascularization. Here, however, we show by cell-specific depletion of Vhl in a mouse model of retinal ischemia (oxygen-induced retinopathy, OIR) that myeloid-derived HIFs promote VEGF and bFGF expression and enhance vascular regeneration in association with improved density and organization of the astrocytic network.

Age-related murine hippocampal CA1 laminae oxidative stress measured in vivo by QUEnch-assiSTed (QUEST) MRI: impact of isoflurane anesthesia - Bruce A. Berkowitz; Robert H. Podolsky; Karen Lins Childers; Alexander Gow; Brandy L. Schneider; Scott C. Lloyd; Kelly E. Bosse; Alana C. Conti; Robin Roberts; Ali M. Berri; Emma Graffice; Kenan Sinan; et al. (GeroScience, 2020)
Age-related impairments in spatial learning and memory often precede non-familial neurodegenerative disease. Ex vivo studies suggest that physiologic age-related oxidative stress in hippocampus area CA1 may contribute to prodromal spatial disorientation and to morbidity. Yet, conventional blood or cerebrospinal fluid assays appear insufficient for early detection or management of oxidative stress within CA1 sub-regions in vivo. Here, we address this biomarker problem using a non-invasive MRI index of CA1 laminae oxidative stress based on reduction in R1 (= 1/T1) after anti-oxidant administration. An R1 reduction reflects quenching of continuous and excessive production of endogenous paramagnetic free radicals. Careful motion-correction image acquisition, and avoiding repeated exposure to isoflurane, facilitates detection of hippocampus CA1 laminae oxidative stress with QUEnch-assiSTed (QUEST) MRI. Intriguingly, age- and isoflurane-related oxidative stress is localized to the stratum lacunosum of the CA1 region. Our data raise the possibility of using QUEST MRI and FDA-approved anti-oxidants to remediate spatial disorientation and later neurodegeneration with age in animals and humans.

Quantitative trait loci and differential gene expression analyses reveal the genetic basis for negatively associated β-carotene and starch content in hexaploid sweetpotato [Ipomoea batatas (L.) Lam.] - Dorcus C. Gemenet; Guilherme da Silva Pereira; Bert De Boeck; Joshua C. Wood; Marcelo Mollinari; Bode A. Olukolu; Federico Diaz; Veronica Mosquera; Reuben T. Ssali; Maria David; Mercy N. Kitavi; Gabriela Burgos; et al. (Theoretical and Applied Genetics, 2020)
Key message β-Carotene content in sweetpotato is associated with the Orange and phytoene synthase genes; due to physical linkage of phytoene synthase with sucrose synthase , β-carotene and starch content are negatively correlated. Abstract In populations depending on sweetpotato for food security, starch is an important source of calories, while β-carotene is an important source of provitamin A. The negative association between the two traits contributes to the low nutritional quality of sweetpotato consumed, especially in sub-Saharan Africa. Using a biparental mapping population of 315 F 1 progeny generated from a cross between an orange-fleshed and a non-orange-fleshed sweetpotato variety, we identified two major quantitative trait loci (QTL) on linkage group (LG) three (LG3) and twelve (LG12) affecting starch, β-carotene, and their correlated traits, dry matter and flesh color. Analysis of parental haplotypes indicated that these two regions acted pleiotropically to reduce starch content and increase β-carotene in genotypes carrying the orange-fleshed parental haplotype at the LG3 locus. Phytoene synthase and sucrose synthase, the rate-limiting and linked genes located within the QTL on LG3 involved in the carotenoid and starch biosynthesis, respectively, were differentially expressed in Beauregard versus Tanzania storage roots. The Orange gene, the molecular switch for chromoplast biogenesis, located within the QTL on LG12 while not differentially expressed was expressed in developing roots of the parental genotypes. We conclude that these two QTL regions act together in a cis and trans manner to inhibit starch biosynthesis in amyloplasts and enhance chromoplast biogenesis, carotenoid biosynthesis, and accumulation in orange-fleshed sweetpotato. Understanding the genetic basis of this negative association between starch and β-carotene will inform future sweetpotato breeding strategies targeting sweetpotato for food and nutritional security.

Bioextractive Removal of Nitrogen by Oysters in Great Bay Piscataqua River Estuary, New Hampshire, USA - Suzanne B. Bricker; Raymond E. Grizzle; Philip Trowbridge; Julie M. Rose; Joao G. Ferreira; Katharine Wellman; Changbo Zhu; Eve Galimany; Gary H. Wikfors; Camille Saurel; Robin Landeck Miller; James Wands; et al. (Estuaries and Coasts, 2020)
Eutrophication is a challenge to coastal waters around the globe. In many places, nutrient reductions from land-based sources have not been sufficient to achieve desired water quality improvements. Bivalve shellfish have shown promise as an in-water strategy to complement land-based nutrient management. A local-scale production model was used to estimate oyster ( Crassostrea virginica ) harvest and bioextraction of nitrogen (N) in Great Bay Piscataqua River Estuary (GBP), New Hampshire, USA, because a system-scale ecological model was not available. Farm-scale N removal results (0.072 metric tons acre −1 year −1 ) were up-scaled to provide a system-wide removal estimate for current (0.61 metric tons year −1 ), and potential removal (2.35 metric tons year −1 ) at maximum possible expansion of licensed aquaculture areas. Restored reef N removal was included to provide a more complete picture. Nitrogen removal through reef sequestration was ~ 3 times that of aquaculture. Estimated reef-associated denitrification, based on previously reported rates, removed 0.19 metric tons N year −1 . When all oyster processes (aquaculture and reefs) were included, N removal was 0.33% and 0.54% of incoming N for current and expanded acres, respectively. An avoided cost approach, with wastewater treatment as the alternative management measure, was used to estimate the value of the N removed. The maximum economic value for aquaculture-based removal was $105,000 and $405,000 for current and expanded oyster areas, respectively. Combined aquaculture and reef restoration is suggested to maximize N reduction capacity while limiting use conflicts. Comparison of removal based on per oyster N content suggests much lower removal rates than model results, but model harvest estimates are similar to reported harvest. Though results are specific to GBP, the approach is transferable to estuaries that support bivalve aquaculture but do not have complex system-scale hydrodynamic or ecological models.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Relationships Between Absolute and Relative Strength and Power in Male Police Officers of Varying Strength Levels - J. Jay Dawes; Robert G. Lockie; Charles L. Kornhauser; Ryan J. Holmes; Robin M. Orr (Journal of Science in Sport and Exercise, 2019)

Hydrogeology of an alpine talus aquifer: Cordillera Blanca, Peru - Robin Glas; Laura Lautz; Jeffrey McKenzie; Robert Moucha; Daniel Chavez; Bryan Mark; John W. Lane (Hydrogeology Journal, 2019)

Impacts of acidification on brown trout Salmo trutta populations and the contribution of stocking to population recovery and genetic diversity - Paulo A. Prodöhl; Andrew Ferguson; Caroline R. Bradley; Robin Ade; Colin Roberts; E. J. Keay; Artur R. Costa; Rosaleen Hynes (Journal of Fish Biology, 2019)
Anthropogenic acidification in SW‐Scotland, from the early 19th Century onwards, led to the extinction of several loch (lake) brown trout ( Salmo trutta ) populations and substantial reductions in numbers in many others. Higher altitude populations with no stocking influence, which are isolated above natural and artificial barriers and subjected to the greatest effect of acidification, exhibited the least intrapopulation genetic diversity (34% of the allelic richness of the populations accessible to anadromous S. trutta ). These, however, were characterised by the greatest interpopulation divergence (highest pairwise D EST 0.61 and F ST 0.53 in contemporary samples) based on 16 microsatellite loci and are among the most differentiated S. trutta populations in NW‐Europe. Five lochs above impassable waterfalls, where S. trutta were thought to be extinct, are documented as having been stocked in the late 1980s or 1990s. All five lochs now support self‐sustaining S. trutta populations; three as a direct result of restoration stocking and two adjoining lochs largely arising from a small remnant wild population in one, but with some stocking input. The genetically unique Loch Grannoch S. trutta , which has been shown to have a heritable increased tolerance to acid conditions, was successfully used as a donor stock to restore populations in two acidic lochs. Loch Fleet S. trutta , which were re‐established from four separate donor sources in the late 1980s, showed differential contribution from these ancestors and a higher genetic diversity than all 17 natural loch populations examined in the area. Genetically distinct inlet and outlet spawning S. trutta populations were found in this loch. Three genetically distinct sympatric populations of S. trutta were identified in Loch Grannoch, most likely representing recruitment from the three main spawning rivers. A distinct genetic signature of Loch Leven S. trutta , the progenitor of many Scottish farm strains, facilitated detection of stocking with these strains. One artificially created loch was shown to have a population genetically very similar to Loch Leven S. trutta . In spite of recorded historical supplemental stocking with Loch Leven derived farm strains, much of the indigenous S. trutta genetic diversity in the area remains intact, aside from the effects of acidification induced bottlenecks. Overall genetic diversity and extant populations have been increased by allochthonous stocking.

Delivering Sustained, Coordinated, and Integrated Observations of the Southern Ocean for Global Impact - Louise Newman; Petra Heil; Rowan Trebilco; Katsuro Katsumata; Andrew Constable; Esmee van Wijk; Karen Assmann; Joana Beja; Phillippa Bricher; Richard Coleman; Daniel Costa; Steve Diggs; et al. (Frontiers in Marine Science, 2019)

Rapid mapping of the spatial and temporal intensity of influenza - David J. Muscatello; Robert Neil F. Leong; Robin M. Turner; Anthony T. Newall (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Lifetime alcohol intake and pancreatic cancer incidence and survival: findings from the Melbourne Collaborative Cohort Study - Harindra Jayasekara; Dallas R. English; Allison M. Hodge; Robin Room; John L. Hopper; Roger L. Milne; Graham G. Giles; Robert J. MacInnis (Cancer Causes & Control, 2019)

Genomics, environment and balancing selection in behaviourally bimodal populations: The caribou case - Maria Cavedon; Chrysoula Gubili; Elizabeth Heppenheimer; Bridgett vonHoldt; Stefano Mariani; Mark Hebblewhite; Troy Hegel; Dave Hervieux; Robert Serrouya; Robin Steenweg; Byron V. Weckworth; Marco Musiani (Molecular Ecology, 2019)
Selection forces that favour different phenotypes in different environments can change frequencies of genes between populations along environmental clines. Clines are also compatible with balancing forces, such as negative frequency‐dependent selection (NFDS), which maintains phenotypic polymorphisms within populations. For example, NFDS is hypothesized to maintain partial migration, a dimorphic behavioural trait prominent in species where only a fraction of the population seasonally migrates. Overall, NFDS is believed to be a common phenomenon in nature, yet a scarcity of studies were published linking naturally occurring allelic variation with bimodal or multimodal phenotypes and balancing selection. We applied a Pool‐seq approach and detected selection on alleles associated with environmental variables along a North–South gradient in western North American caribou, a species displaying partially migratory behaviour. On 51 loci, we found a signature of balancing selection, which could be related to NFDS and ultimately the maintenance of the phenotypic polymorphisms known within these populations. Yet, remarkably, we detected directional selection on a locus when our sample was divided into two behaviourally distinctive groups regardless of geographic provenance (a subset of GPS‐collared migratory or sedentary individuals), indicating that, within populations, phenotypically homogeneous groups were genetically distinctive. Loci under selection were linked to functional genes involved in oxidative stress response, body development and taste perception. Overall, results indicated genetic differentiation along an environmental gradient of caribou populations, which we found characterized by genes potentially undergoing balancing selection. We suggest that the underlining balancing force, NFDS, plays a strong role within populations harbouring multiple haplotypes and phenotypes, as it is the norm in animals, plants and humans too.

Data Maturity Assessment – Bewertung der Reife des Datenmanagements für Smart Maintenance - Robert Bernerstätter; Robin Kühnast (BHM Berg- und Hüttenmännische Monatshefte, 2019)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Assessment of Nannochloropsis gaditana growth and lipid accumulation with increased inorganic carbon delivery - Todd C. Pedersen; Robert D. Gardner; Robin Gerlach; Brent M. Peyton (Journal of Applied Phycology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Associations between cyanobacteria and indices of secondary production in the western basin of Lake Erie - James H. Larson; Mary Anne Evans; Robert J. Kennedy; Sean W. Bailey; Keith A. Loftin; Zachary R. Laughrey; Robin A. Femmer; Jeff S. Schaeffer; William B. Richardson; Timothy T. Wynne; J. C. Nelson; Joseph W. Duris (Limnology and Oceanography, 2018)
Large lakes provide a variety of ecological services to surrounding cities and communities. Many of these services are supported by ecological processes that are threatened by the increasing prevalence of cyanobacterial blooms which occur as aquatic ecosystems experience cultural eutrophication. Over the past 10 yr, Lake Erie experienced cyanobacterial blooms of increasing severity and frequency, which have resulted in impaired drinking water for the surrounding communities. Cyanobacterial blooms may impact ecological processes that support other services, but many of these impacts have not been documented. Secondary production (production of primary consumers) is an important process that supports economically important higher trophic levels. Cyanobacterial blooms may influence secondary production because cyanobacteria are a poor‐quality food resource and cyanotoxins may be harmful to consumers. Over 3 yr at 34 sites across the western basin of Lake Erie, we measured three indices of secondary production that focus on the dominant bivalve taxa: (1) growth of a native unionid mussel, (2) the size of young‐of‐year dreissenid mussels, and (3) the mass of colonizing animals on a Hester‐Dendy sampler. Associations between these indices and cyanobacterial data were estimated to assess whether cyanobacteria are associated with variation in secondary production in the western basin of Lake Erie. The results suggest cyanobacterial abundance alone is only weakly associated with secondary production, but that cyanotoxins have a larger effect on secondary production. Given recurring late‐summer cyanobacterial blooms, this impact on secondary production has the potential to undermine Lake Erie's ability to sustain important ecosystem services.

Brain structural and functional asymmetry in human situs inversus totalis - Guy Vingerhoets; Xiang Li; Lewis Hou; Stephanie Bogaert; Helena Verhelst; Robin Gerrits; Roma Siugzdaite; Neil Roberts (Brain Structure and Function, 2018)

The prostate cancer screening clinic in the Bahamas: a model for low- and middle-income countries - Robin Roberts; Corydon Mitchell; Ana Lourdes Tancawan; Mandi Pedican; Glenn Wayne Jones (Cancer Causes & Control, 2017)

Cancer in populations of African Ancestry: studies of the African Caribbean Cancer Consortium - Camille Ragin; Elizabeth Blackman; Robin Roberts; Raleigh Butler; Samuel Gathere; Darron Halliday; Kimlin Ashing (Cancer Causes & Control, 2017)

Outcomes of treatment in men with prostate cancer at the cancer centre Bahamas - Glenn Wayne Jones; Osama Kellini; Robin Roberts; Nevein Girgis; Chelsea Brown; Krista Nottage; Thomas McGowan; Corrine Sin Quee-Brown; Conville Brown (Cancer Causes & Control, 2017)

Deciphering the enigma of undetected species, phylogenetic, and functional diversity based on Good‐Turing theory - Anne Chao; Chun‐Huo Chiu; Robert K. Colwell; Luiz Fernando S. Magnago; Robin L. Chazdon; Nicholas J. Gotelli (Ecology, 2017)
Estimating the species, phylogenetic, and functional diversity of a community is challenging because rare species are often undetected, even with intensive sampling. The Good‐Turing frequency formula, originally developed for cryptography, estimates in an ecological context the true frequencies of rare species in a single assemblage based on an incomplete sample of individuals. Until now, this formula has never been used to estimate undetected species, phylogenetic, and functional diversity. Here, we first generalize the Good‐Turing formula to incomplete sampling of two assemblages. The original formula and its two‐assemblage generalization provide a novel and unified approach to notation, terminology, and estimation of undetected biological diversity. For species richness, the Good‐Turing framework offers an intuitive way to derive the non‐parametric estimators of the undetected species richness in a single assemblage, and of the undetected species shared between two assemblages. For phylogenetic diversity, the unified approach leads to an estimator of the undetected Faith's phylogenetic diversity ( PD , the total length of undetected branches of a phylogenetic tree connecting all species), as well as a new estimator of undetected PD shared between two phylogenetic trees. For functional diversity based on species traits, the unified approach yields a new estimator of undetected Walker et al.'s functional attribute diversity ( FAD , the total species‐pairwise functional distance) in a single assemblage, as well as a new estimator of undetected FAD shared between two assemblages. Although some of the resulting estimators have been previously published (but derived with traditional mathematical inequalities), all taxonomic, phylogenetic, and functional diversity estimators are now derived under the same framework. All the derived estimators are theoretically lower bounds of the corresponding undetected diversities; our approach reveals the sufficient conditions under which the estimators are nearly unbiased, thus offering new insights. Simulation results are reported to numerically verify the performance of the derived estimators. We illustrate all estimators and assess their sampling uncertainty with an empirical dataset for Brazilian rain forest trees. These estimators should be widely applicable to many current problems in ecology, such as the effects of climate change on spatial and temporal beta diversity and the contribution of trait diversity to ecosystem multi‐functionality.

Continuing influences of introduced hedgehogs Erinaceus europaeus as a predator of wader (Charadrii) eggs four decades after their release on the Outer Hebrides, Scotland - John Calladine; Elizabeth M. Humphreys; Lucy Gilbert; Robert W. Furness; Robert A. Robinson; Robert J. Fuller; Nick A. Littlewood; Robin J. Pakeman; Johanne Ferguson; Charles Thompson (Biological Invasions, 2017)

Metal-contaminated potato crops and potential human health risk in Bolivian mining highlands - Alan E. Garrido; William H. J. Strosnider; Robin Taylor Wilson; Janette Condori; Robert W. Nairn (Environmental Geochemistry and Health, 2017)

The population genetics of two orchid bees suggests high dispersal, low diploid male production and only an effect of island isolation in lowering genetic diversity - Antonella Soro; J. Javier G. Quezada-Euan; Panagiotis Theodorou; Robin F. A. Moritz; Robert J. Paxton (Conservation Genetics, 2017)

Whole grain in manufactured foods: Current use, challenges and the way forward - Christelle Schaffer-Lequart; Undine Lehmann; Alastair B. Ross; Olivier Roger; Alison L. Eldridge; Edwin Ananta; Marie-France Bietry; Luis R. King; Alice V. Moroni; Sathaporn Srichuwong; Anne-Sophie Wavreille; Robert Redgwell; et al. (Critical Reviews in Food Science and Nutrition, 2017)

The unseen invaders: introduced earthworms as drivers of change in plant communities in North American forests (a meta‐analysis) - Dylan Craven; Madhav P. Thakur; Erin K. Cameron; Lee E. Frelich; Robin Beauséjour; Robert B. Blair; Bernd Blossey; James Burtis; Amy Choi; Andrea Dávalos; Timothy J. Fahey; Nicholas A. Fisichelli; et al. (Global Change Biology, 2017)
Globally, biological invasions can have strong impacts on biodiversity as well as ecosystem functioning. While less conspicuous than introduced aboveground organisms, introduced belowground organisms may have similarly strong effects. Here, we synthesize for the first time the impacts of introduced earthworms on plant diversity and community composition in North American forests. We conducted a meta‐analysis using a total of 645 observations to quantify mean effect sizes of associations between introduced earthworm communities and plant diversity, cover of plant functional groups, and cover of native and non‐native plants. We found that plant diversity significantly declined with increasing richness of introduced earthworm ecological groups. While plant species richness or evenness did not change with earthworm invasion, our results indicate clear changes in plant community composition: cover of graminoids and non‐native plant species significantly increased, and cover of native plant species (of all functional groups) tended to decrease, with increasing earthworm biomass. Overall, these findings support the hypothesis that introduced earthworms facilitate particular plant species adapted to the abiotic conditions of earthworm‐invaded forests. Further, our study provides evidence that introduced earthworms are associated with declines in plant diversity in North American forests. Changing plant functional composition in these forests may have long‐lasting effects on ecosystem functioning.

On the sustainability of inland fisheries: Finding a future for the forgotten - Steven J. Cooke; Edward H. Allison; T. Douglas Beard; Robert Arlinghaus; Angela H. Arthington; Devin M. Bartley; Ian G. Cowx; Carlos Fuentevilla; Nancy J. Leonard; Kai Lorenzen; Abigail J. Lynch; Vivian M. Nguyen; et al. (Ambio, 2016)

Redrawing the map: mt DNA provides new insight into the distribution and diversity of short‐finned pilot whales in the Pacific Ocean - Amy M. Van Cise; Phillip A. Morin; Robin W. Baird; Aimee R. Lang; Kelly M. Robertson; Susan J. Chivers; Robert L. Brownell; Karen K. Martien (Marine Mammal Science, 2016)
Correlations between morphological and genetic data provide evidence to delineate species or evolutionarily significant units, which then become the units to conserve in management plans. Here, we examine the distribution and genetic differentiation of two morphotypes of short‐finned pilot whale ( Globicephala macrorhynchus ) in the Pacific Ocean. Mitochondrial control region sequences from 333 samples were combined with 152 previously published sequences to describe genetic variability globally and population structure in the Pacific. Although genetic variability is low, we found strong differentiation at both broad and local levels across the Pacific. Based on genetics, two types are distributed throughout the Pacific, one predominantly in the eastern Pacific and the other in the western and central Pacific. In the eastern Pacific Ocean, no correlation was found between distribution and sea surface temperature. The two types have broad latitudinal ranges, suggesting their distributions are likely driven by more complex factors, such as prey distribution, rather than sea surface temperature.

Is breast cancer risk associated with alcohol intake before first full-term pregnancy? - Harindra Jayasekara; Robert J. MacInnis; Allison M. Hodge; Robin Room; Roger L. Milne; John L. Hopper; Graham G. Giles; Dallas R. English (Cancer Causes & Control, 2016)

Differential frequency of NKG2C/KLRC2 deletion in distinct African populations and susceptibility to Trachoma: a new method for imputation of KLRC2 genotypes from SNP genotyping data - Adriana Goncalves; Pateh Makalo; Hassan Joof; Sarah Burr; Athumani Ramadhani; Patrick Massae; Aiweda Malisa; Tara Mtuy; Tamsyn Derrick; Anna R. Last; Meno Nabicassa; Eunice Cassama; et al. (Human Genetics, 2016)

Evidence of the St. Clair-Detroit River System as a dispersal corridor and nursery habitat for transient larval burbot - Darrin E. McCullough; Edward F. Roseman; Kevin M. Keeler; Robin L. DeBruyne; Jeremy J. Pritt; Patricia A. Thompson; Stacey Ireland; Jason E. Ross; Dustin Bowser; Robert D. Hunter; Dana Castle; Jason L. Fischer; et al. (Hydrobiologia, 2015)

The effects of foundation species on community assembly: a global study on alpine cushion plant communities - Zaal Kikvidze; Robin W. Brooker; Bradley J. Butterfield; Ragan M. Callaway; Lohengrin A. Cavieres; Bradley J. Cook; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology, 2015)
Foundation species can change plant community structure by modulating important ecological processes such as community assembly, yet this topic is poorly understood. In alpine systems, cushion plants commonly act as foundation species by ameliorating local conditions. Here, we analyze diversity patterns of species' assembly within cushions and in adjacent surrounding open substrates (83 sites across five continents) calculating floristic dissimilarity between replicate plots, and using linear models to analyze relationships between microhabitats and species diversity. Floristic dissimilarity did not change across biogeographic regions, but was consistently lower in the cushions than in the open microhabitat. Cushion plants appear to enable recruitment of many relatively stress‐intolerant species that otherwise would not establish in these communities, yet the niche space constructed by cushion plants supports a more homogeneous composition of species than the niche space beyond the cushion's influence. As a result, cushion plants support higher α‐diversity and a larger species pool, but harbor assemblies with lower β‐diversity than open microhabitats. We conclude that habitats with and without dominant foundation species can strongly differ in the processes that drive species recruitment, and thus the relationship between local and regional species diversity.

Dynamic firing properties of type I spiral ganglion neurons - Robin L. Davis; Robert A. Crozier (Cell and Tissue Research, 2015)

Distribution of Nitellopsis obtusa (Characeae) in New York, U.S.A. - Robin S. Sleith; Amy J. Havens; Robert A. Stewart; Kenneth G. Karol (Brittonia, 2015)

Unveiling the species‐rank abundance distribution by generalizing the Good‐Turing sample coverage theory - Anne Chao; T. C. Hsieh; Robin L. Chazdon; Robert K. Colwell; Nicholas J. Gotelli (Ecology, 2015)
Based on a sample of individuals, we focus on inferring the vector of species relative abundance of an entire assemblage and propose a novel estimator of the complete species‐rank abundance distribution (RAD). Nearly all previous estimators of the RAD use the conventional “plug‐in” estimator p̂ i (sample relative abundance) of the true relative abundance p i of species i . Because most biodiversity samples are incomplete, the plug‐in estimators are applied only to the subset of species that are detected in the sample. Using the concept of sample coverage and its generalization, we propose a new statistical framework to estimate the complete RAD by separately adjusting the sample relative abundances for the set of species detected in the sample and estimating the relative abundances for the set of species undetected in the sample but inferred to be present in the assemblage. We first show that p̂ i is a positively biased estimator of p i for species detected in the sample, and that the degree of bias increases with increasing relative rarity of each species. We next derive a method to adjust the sample relative abundance to reduce the positive bias inherent in p̂ i . The adjustment method provides a nonparametric resolution to the longstanding challenge of characterizing the relationship between the true relative abundance in the entire assemblage and the observed relative abundance in a sample. Finally, we propose a method to estimate the true relative abundances of the undetected species based on a lower bound of the number of undetected species. We then combine the adjusted RAD for the detected species and the estimated RAD for the undetected species to obtain the complete RAD estimator. Simulation results show that the proposed RAD curve can unveil the true RAD and is more accurate than the empirical RAD. We also extend our method to incidence data. Our formulas and estimators are illustrated using empirical data sets from surveys of forest spiders (for abundance data) and soil ciliates (for incidence data). The proposed RAD estimator is also applicable to estimating various diversity measures and should be widely useful to analyses of biodiversity and community structure.

Bees under stress: sublethal doses of a neonicotinoid pesticide and pathogens interact to elevate honey bee mortality across the life cycle - Vincent Doublet; Maureen Labarussias; Joachim R. de Miranda; Robin F. A. Moritz; Robert J. Paxton (Environmental Microbiology, 2015)
Summary Microbial pathogens are thought to have a profound impact on insect populations. Honey bees are suffering from elevated colony losses in the northern hemisphere possibly because of a variety of emergent microbial pathogens, with which pesticides may interact to exacerbate their impacts. To reveal such potential interactions, we administered at sublethal and field realistic doses one neonicotinoid pesticide (thiacloprid) and two common microbial pathogens, the invasive microsporidian N osema ceranae and black queen cell virus ( BQCV ), individually to larval and adult honey bees in the laboratory. Through fully crossed experiments in which treatments were administered singly or in combination, we found an additive interaction between BQCV and thiacloprid on host larval survival likely because the pesticide significantly elevated viral loads. In adult bees, two synergistic interactions increased individual mortality: between N . ceranae and BQCV , and between N . ceranae and thiacloprid. The combination of two pathogens had a more profound effect on elevating adult mortality than N . ceranae plus thiacloprid. Common microbial pathogens appear to be major threats to honey bees, while sublethal doses of pesticide may enhance their deleterious effects on honey bee larvae and adults. It remains an open question as to whether these interactions can affect colony survival.

Lifetime alcohol consumption and upper aero-digestive tract cancer risk in the Melbourne Collaborative Cohort Study - Harindra Jayasekara; Robert J. MacInnis; Allison M. Hodge; John L. Hopper; Graham G. Giles; Robin Room; Dallas R. English (Cancer Causes & Control, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Islands as model systems in ecology and evolution: prospects fifty years after MacArthur‐Wilson - Ben H. Warren; Daniel Simberloff; Robert E. Ricklefs; Robin Aguilée; Fabien L. Condamine; Dominique Gravel; Hélène Morlon; Nicolas Mouquet; James Rosindell; Juliane Casquet; Elena Conti; Josselin Cornuault; et al. (Ecology Letters, 2015)
The study of islands as model systems has played an important role in the development of evolutionary and ecological theory. The 50th anniversary of MacArthur and Wilson's (December 1963) article, ‘An equilibrium theory of insular zoogeography’, was a recent milestone for this theme. Since 1963, island systems have provided new insights into the formation of ecological communities. Here, building on such developments, we highlight prospects for research on islands to improve our understanding of the ecology and evolution of communities in general. Throughout, we emphasise how attributes of islands combine to provide unusual research opportunities, the implications of which stretch far beyond islands. Molecular tools and increasing data acquisition now permit re‐assessment of some fundamental issues that interested MacArthur and Wilson. These include the formation of ecological networks, species abundance distributions, and the contribution of evolution to community assembly. We also extend our prospects to other fields of ecology and evolution – understanding ecosystem functioning, speciation and diversification – frequently employing assets of oceanic islands in inferring the geographic area within which evolution has occurred, and potential barriers to gene flow. Although island‐based theory is continually being enriched, incorporating non‐equilibrium dynamics is identified as a major challenge for the future.

Structuring international development decisions: confronting trade-offs between land use and community development in Costa Rica - Joseph Árvai; Delanie Kellon; Ramón León; Robin Gregory; Robert Richardson (Environment Systems and Decisions, 2014)

Respiratory Assessment and Use of PPE Among Poultry Workers in NC: A Pilot Study - Gregory D. Kearney; Robert Shaw; Robin Tutor-Marcom; Matthew A. Prentice (Journal of Agromedicine, 2014)

Evaluation of Respiratory Symptoms and Respiratory Protection Behavior Among Poultry Workers in Small Farming Operations - Gregory D. Kearney; Robert Shaw; Matthew Prentice; Robin Tutor-Marcom (Journal of Agromedicine, 2014)

An ecological function and services approach to total maximum daily load (TMDL) prioritization - Robert K. Hall; David Guiliano; Sherman Swanson; Michael J. Philbin; John Lin; Joan L. Aron; Robin J. Schafer; Daniel T. Heggem (Environmental Monitoring and Assessment, 2014)

Growth, nitrogen utilization and biodiesel potential for two chlorophytes grown on ammonium, nitrate or urea - Everett Eustance; Robert D. Gardner; Karen M. Moll; Joseph Menicucci; Robin Gerlach; Brent M. Peyton (Journal of Applied Phycology, 2013)

Biological markers of exposure to organophosphorus nerve agents - Robin M. Black; Robert W. Read (Archives of Toxicology, 2013)

The geology and geochemistry of the Lumwana Cu (± Co ± U) deposits, NW Zambia - Robin Bernau; Stephen Roberts; Mike Richards; Bruce Nisbet; Adrian Boyce; James Nowecki (Mineralium Deposita, 2013)

Use of sodium bicarbonate to stimulate triacylglycerol accumulation in the chlorophyte Scenedesmus sp. and the diatom Phaeodactylum tricornutum - Robert D. Gardner; Keith E. Cooksey; Florence Mus; Richard Macur; Karen Moll; Everett Eustance; Ross P. Carlson; Robin Gerlach; Matthew W. Fields; Brent M. Peyton (Journal of Applied Phycology, 2012)

Corrigendum - CLARE D. MARSDEN; ROSIE WOODROFFE; MICHAEL G. L. MILLS; J. WELDON MCNUTT; SCOTT CREEL; ROSEMARY GROOM; MASENGA EMMANUEL; SARAH CLEAVELAND; PIETER KAT; GREGORY S. A. RASMUSSEN; JOSHUA GINSBERG; ROBIN LINES; et al. (Molecular Ecology, 2012)

Popular misconceptions - ROBERT C. VRIJENHOEK; ROBIN S. WAPLES (Molecular Ecology, 2012)

Seasonal and Annual Fluxes of Nutrients and Organic Matter from Large Rivers to the Arctic Ocean and Surrounding Seas - Robert Max Holmes; James W. McClelland; Bruce J. Peterson; Suzanne E. Tank; Ekaterina Bulygina; Timothy I. Eglinton; Viacheslav V. Gordeev; Tatiana Y. Gurtovaya; Peter A. Raymond; Daniel J. Repeta; Robin Staples; Robert G. Striegl; et al. (Estuaries and Coasts, 2012)

Infection not associated with use of human musculoskeletal tissue allografts - Robert K. Eastlack; Thomas J. Kesman; Robin Patel; Paul M. Huddleston (Cell and Tissue Banking, 2012)

Spatial and temporal patterns of neutral and adaptive genetic variation in the endangered African wild dog ( Lycaon pictus ) - CLARE D. MARSDEN; ROSIE WOODROFFE; MICHAEL G. L. MILLS; J. WELDON McNUTT; SCOTT CREEL; ROSEMARY GROOM; MASENGA EMMANUEL; SARAH CLEAVELAND; PIETER KAT; GREGORY S.A. RASMUSSEN; JOSHUA GINSBERG; ROBIN LINES; et al. (Molecular Ecology, 2012)
Deciphering patterns of genetic variation within a species is essential for understanding population structure, local adaptation and differences in diversity between populations. Whilst neutrally evolving genetic markers can be used to elucidate demographic processes and genetic structure, they are not subject to selection and therefore are not informative about patterns of adaptive variation. As such, assessments of pertinent adaptive loci, such as the immunity genes of the major histocompatibility complex (MHC), are increasingly being incorporated into genetic studies. In this study, we combined neutral (microsatellite, mtDNA) and adaptive (MHC class II DLA‐DRB1 locus) markers to elucidate the factors influencing patterns of genetic variation in the African wild dog ( Lycaon pictus ); an endangered canid that has suffered extensive declines in distribution and abundance. Our genetic analyses found all extant wild dog populations to be relatively small ( N e

A novel statistical method for classifying habitat generalists and specialists - Robin L. Chazdon; Anne Chao; Robert K. Colwell; Shang-Yi Lin; Natalia Norden; Susan G. Letcher; David B. Clark; Bryan Finegan; J. Pablo Arroyo (Ecology, 2011)
We develop a novel statistical approach for classifying generalists and specialists in two distinct habitats. Using a multinomial model based on estimated species relative abundance in two habitats, our method minimizes bias due to differences in sampling intensities between two habitat types as well as bias due to insufficient sampling within each habitat. The method permits a robust statistical classification of habitat specialists and generalists, without excluding rare species a priori. Based on a user‐defined specialization threshold, the model classifies species into one of four groups: (1) generalist; (2) habitat A specialist; (3) habitat B specialist; and (4) too rare to classify with confidence. We illustrate our multinomial classification method using two contrasting data sets: (1) bird abundance in woodland and heath habitats in southeastern Australia and (2) tree abundance in second‐growth (SG) and old‐growth (OG) rain forests in the Caribbean lowlands of northeastern Costa Rica. We evaluate the multinomial model in detail for the tree data set. Our results for birds were highly concordant with a previous nonstatistical classification, but our method classified a higher fraction (57.7%) of bird species with statistical confidence. Based on a conservative specialization threshold and adjustment for multiple comparisons, 64.4% of tree species in the full sample were too rare to classify with confidence. Among the species classified, OG specialists constituted the largest class (40.6%), followed by generalist tree species (36.7%) and SG specialists (22.7%). The multinomial model was more sensitive than indicator value analysis or abundance‐based phi coefficient indices in detecting habitat specialists and also detects generalists statistically. Classification of specialists and generalists based on rarefied subsamples was highly consistent with classification based on the full sample, even for sampling percentages as low as 20%. Major advantages of the new method are (1) its ability to distinguish habitat generalists (species with no significant habitat affinity) from species that are simply too rare to classify and (2) applicability to a single representative sample or a single pooled set of representative samples from each of two habitat types. The method as currently developed can be applied to no more than two habitats at a time.

The use of a zinc-efficient wheat cultivar as an adaptation to calcareous subsoil: a glasshouse study - Robert E. Holloway; Robin D. Graham; Therese M. McBeath; Dot M. Brace (Plant and Soil, 2010)

Efficacy is a contributing factor to the clinical onset of bronchodilation of inhaled β2-adrenoceptor agonists - Elizabeth M. Rosethorne; Robert J. Turner; Robin A. Fairhurst; Steven J. Charlton (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

How Do Cancer Patients Navigate the Public Information Environment? Understanding Patterns and Motivations for Movement Among Information Sources - Rebekah H. Nagler; Anca Romantan; Bridget J. Kelly; Robin S. Stevens; Stacy W. Gray; Shawnika J. Hull; A. Susana Ramirez; Robert C. Hornik (Journal of Cancer Education, 2010)

In-Street Wind Direction Variability in the Vicinity of a Busy Intersection in Central London - Ahmed A. Balogun; Alison S. Tomlin; Curtis R. Wood; Janet F. Barlow; Stephen E. Belcher; Robert J. Smalley; Justin J. N. Lingard; Sam J. Arnold; Adrian Dobre; Alan G. Robins; Damien Martin; Dudley E. Shallcross (Boundary-Layer Meteorology, 2010)

Common goals: policy implications of DNA barcoding as a protocol for identification of arthropod pests - Robin Floyd; João Lima; Jeremy deWaard; Leland Humble; Robert Hanner (Biological Invasions, 2010)

Estimating the Density of Honeybee Colonies across Their Natural Range to Fill the Gap in Pollinator Decline Censuses - RODOLFO JAFFÉ; VINCENT DIETEMANN; MIKE H. ALLSOPP; CECILIA COSTA; ROBIN M. CREWE; RAFFAELE DALL’OLIO; PILAR DE LA RÚA; MOGBEL A. A. EL‐NIWEIRI; INGEMAR FRIES; NIKOLA KEZIC; MICHAEL S. MEUSEL; ROBERT J. PAXTON; et al. (Conservation Biology, 2010)
Although pollinator declines are a global biodiversity threat, the demography of the western honeybee ( Apis mellifera ) has not been considered by conservationists because it is biased by the activity of beekeepers. To fill this gap in pollinator decline censuses and to provide a broad picture of the current status of honeybees across their natural range, we used microsatellite genetic markers to estimate colony densities and genetic diversity at different locations in Europe, Africa, and central Asia that had different patterns of land use. Genetic diversity and colony densities were highest in South Africa and lowest in Northern Europe and were correlated with mean annual temperature. Confounding factors not related to climate, however, are also likely to influence genetic diversity and colony densities in honeybee populations. Land use showed a significantly negative influence over genetic diversity and the density of honeybee colonies over all sampling locations. In Europe honeybees sampled in nature reserves had genetic diversity and colony densities similar to those sampled in agricultural landscapes, which suggests that the former are not wild but may have come from managed hives. Other results also support this idea: putative wild bees were rare in our European samples, and the mean estimated density of honeybee colonies on the continent closely resembled the reported mean number of managed hives. Current densities of European honeybee populations are in the same range as those found in the adverse climatic conditions of the Kalahari and Saharan deserts, which suggests that beekeeping activities do not compensate for the loss of wild colonies. Our findings highlight the importance of reconsidering the conservation status of honeybees in Europe and of regarding beekeeping not only as a profitable business for producing honey, but also as an essential component of biodiversity conservation.

Biomarkers of organophosphorus nerve agent exposure: comparison of phosphylated butyrylcholinesterase and phosphylated albumin after oxime therapy - Robert W. Read; James R. Riches; Jacqueline A. Stevens; Sarah J. Stubbs; Robin M. Black (Archives of Toxicology, 2010)

Vulnerability and Resilience of Tropical Forest Species to Land‐Use Change - NIGEL E. STORK; JONATHAN A. CODDINGTON; ROBERT K. COLWELL; ROBIN L. CHAZDON; CHRISTOPHER W. DICK; CARLOS A. PERES; SEAN SLOAN; KATHY WILLIS (Conservation Biology, 2009)
We provide a cross‐taxon and historical analysis of what makes tropical forest species vulnerable to extinction. Several traits have been important for species survival in the recent and distant geological past, including seed dormancy and vegetative growth in plants, small body size in mammals, and vagility in insects. For major past catastrophes, such as the five mass extinction events, large range size and vagility or dispersal were key to species survival. Traits that make some species more vulnerable to extinction are consistent across time scales. Terrestrial organisms, particularly animals, are more extinction prone than marine organisms. Plants that persist through dramatic changes often reproduce vegetatively and possess mechanisms of die back. Synergistic interactions between current anthropogenic threats, such as logging, fire, hunting, pests and diseases, and climate change are frequent. Rising temperatures threaten all organisms, perhaps particularly tropical organisms adapted to small temperature ranges and isolated by distance from suitable future climates. Mutualist species and trophic specialists may also be more threatened because of such range‐shift gaps. Phylogenetically specialized groups may be collectively more prone to extinction than generalists. Characterization of tropical forest species’ vulnerability to anthropogenic change is constrained by complex interactions among threats and by both taxonomic and ecological impediments, including gross undersampling of biotas and poor understanding of the spatial patterns of taxa at all scales.

Prospects for tropical forest biodiversity in a human‐modified world - Toby A. Gardner; Jos Barlow; Robin Chazdon; Robert M. Ewers; Celia A. Harvey; Carlos A. Peres; Navjot S. Sodhi (Ecology Letters, 2009)
The future of tropical forest biodiversity depends more than ever on the effective management of human‐modified landscapes, presenting a daunting challenge to conservation practitioners and land use managers. We provide a critical synthesis of the scientific insights that guide our understanding of patterns and processes underpinning forest biodiversity in the human‐modified tropics, and present a conceptual framework that integrates a broad range of social and ecological factors that define and contextualize the possible future of tropical forest species. A growing body of research demonstrates that spatial and temporal patterns of biodiversity are the dynamic product of interacting historical and contemporary human and ecological processes. These processes vary radically in their relative importance within and among regions, and have effects that may take years to become fully manifest. Interpreting biodiversity research findings is frequently made difficult by constrained study designs, low congruence in species responses to disturbance, shifting baselines and an over‐dependence on comparative inferences from a small number of well studied localities. Spatial and temporal heterogeneity in the potential prospects for biodiversity conservation can be explained by regional differences in biotic vulnerability and anthropogenic legacies, an ever‐tighter coupling of human‐ecological systems and the influence of global environmental change. These differences provide both challenges and opportunities for biodiversity conservation. Building upon our synthesis we outline a simple adaptive‐landscape planning framework that can help guide a new research agenda to enhance biodiversity conservation prospects in the human‐modified tropics.

Phosphylated tyrosine in albumin as a biomarker of exposure to organophosphorus nerve agents - Nichola H. Williams; John M. Harrison; Robert W. Read; Robin M. Black (Archives of Toxicology, 2007)

Understanding Anglers’ Preferences for Fishing Tournament Characteristics and Policies - Chi-Ok Oh; Robert B. Ditton; Robin Riechers (Environmental Management, 2007)

Tuareg, a novel miniature-inverted repeat family of pearl millet (Pennisetum glaucum) related to the PIF superfamily of maize - Marie-Stanislas Remigereau; Odile Robin; Sonia Siljak-Yakovlev; Aboubakry Sarr; Thierry Robert; Thierry Langin (Genetica, 2006)

DNA and meristic evidence for two species of giant stargazer (Teleostei: Uranoscopidae: Kathetostoma) in New Zealand waters - Peter J. Smith; Robin P. McPhee; Clive D. Roberts (New Zealand Journal of Marine and Freshwater Research, 2006)
The taxonomic status of the banded giant stargazer in New Zealand waters is uncertain. Mitochondrial DNA partial sequences of the cytochrome b gene and the control region, along with three meristic characters (numbers of dorsal fin rays, anal fin rays, and vertebrae), were compared among six recognised species of Kathetostoma and specimens of the banded giant morph. New Zealand specimens referred to as banded giant stargazer were shown to be a discrete species distinguished from the giant stargazer K. giganteum from New Zealand and the banded K. laeve and K. canaster from Australia, by cytochrome b and control region sequences and meristic counts. This undescribed species occurs over a wide geographic range from the Snares shelf (48°S) to the Norfolk Ridge (32°S) in the Tasman Sea, and is largely sympatric with K. giganteum. The two New Zealand species occupy different depth ranges, with the banded giant stargazer generally occurring in shallower water ( K. giganteum (12–1000 m).

Letdowns, Wake-Up Calls, and Constructed Preferences: People’s Responses to Fuel and Wildfire Risks - Joseph Arvai; Robin Gregory; Dan Ohlson; Bruce Blackwell; Robert Gray (Journal of Forestry, 2006)
This article presents results from three studies, which seek to develop a better understanding of some of the difficulties faced by forest managers in making wildfire risk management decisions. Study 1 showed that both the experts and the public tend to emphasize uncontrollable factors when asked to consider the causes of wildfires. Study 2 revealed the large role played by emotional responses in judgments about wildfire risks. Study 3 showed that preferences for risk management options tend to be remarkably malleable in response to even slight shifts in framing. In contrast to previous studies that call for improved public education about wildfire, our results emphasize the need to introduce improved processes to inform both expert and public decisionmaking for fire risk management.

Formulation of a dry powder influenza vaccine for nasal delivery - Robert J. Garmise; Kevin Mar; Timothy M. Crowder; C. Robin Hwang; Matthew Ferriter; Juan Huang; John A. Mikszta; Vincent J. Sullivan; Anthony J. Hickey (AAPS PharmSciTech, 2006)

Biomass and Decay Rates of Roots and Detritus in Sediments of Intermittent Coastal Plain Streams - Ken M. Fritz; Jack W. Feminella; Chris Colson; B. Graeme Lockaby; Robin Governo; Robert B. Rummer (Hydrobiologia, 2006)

Aluminum-tolerant Pseudomonas fluorescens: ROS toxicity and enhanced NADPH production - Ranji Singh; Robin Beriault; Jeffrey Middaugh; Robert Hamel; Daniel Chenier; Vasu D. Appanna; Sergey Kalyuzhnyi (Extremophiles, 2005)

A new statistical approach for assessing similarity of species composition with incidence and abundance data - Anne Chao; Robin L. Chazdon; Robert K. Colwell; Tsung‐Jen Shen (Ecology Letters, 2005)
The classic Jaccard and Sørensen indices of compositional similarity (and other indices that depend upon the same variables) are notoriously sensitive to sample size, especially for assemblages with numerous rare species. Further, because these indices are based solely on presence–absence data, accurate estimators for them are unattainable. We provide a probabilistic derivation for the classic, incidence‐based forms of these indices and extend this approach to formulate new Jaccard‐type or Sørensen‐type indices based on species abundance data. We then propose estimators for these indices that include the effect of unseen shared species, based on either (replicated) incidence‐ or abundance‐based sample data. In sampling simulations, these new estimators prove to be considerably less biased than classic indices when a substantial proportion of species are missing from samples. Based on species‐rich empirical datasets, we show how incorporating the effect of unseen shared species not only increases accuracy but also can change the interpretation of results.

The area requirements of an ecosystem service: crop pollination by native bee communities in California - Claire Kremen; Neal M. Williams; Robert L. Bugg; John P. Fay; Robin W. Thorp (Ecology Letters, 2004)
Managing ecosystem services is critical to human survival, yet we do not know how large natural areas must be to support these services. We investigated how crop pollination services provided by native, unmanaged, bee communities varied on organic and conventional farms situated along a gradient of isolation from natural habitat. Pollination services from native bees were significantly, positively related to the proportion of upland natural habitat in the vicinity of farm sites, but not to any other factor studied, including farm type, insecticide usage, field size and honeybee abundance. The scale of this relationship matched bee foraging ranges. Stability and predictability of pollination services also increased with increasing natural habitat area. This strong relationship between natural habitat area and pollination services was robust over space and time, allowing prediction of the area needed to produce a given level of pollination services by wild bees within this landscape.

Analysis of the Maize Polyubiquitin-1 Promoter Heat Shock Elements and Generation of Promoter Variants with Modified Expression Characteristics - Stephen J. Streatfield; Maria E. Magallanes-Lundback; Katherine K. Beifuss; Christopher A. Brooks; Robin L. Harkey; Robert T. Love; Jeff Bray; John A. Howard; Joseph M. Jilka; Elizabeth E. Hood (Transgenic Research, 2004)

Effect of Network Topology on Relative Permeability - Ji-Youn Arns; Vanessa Robins; Adrian P. Sheppard; Robert M. Sok; W. V. Pinczewski; Mark A. Knackstedt (Transport in Porous Media, 2004)

A small molecule antagonist of the α v β3 integrin suppresses MDA-MB-435 skeletal metastasis - John F. Harms; Danny R. Welch; Rajeev S. Samant; Lalita A. Shevde; Mary E. Miele; Geetha R. Babu; Steven F. Goldberg; Virginia R. Gilman; Donna M. Sosnowski; Dianalee A. Campo; Carol V. Gay; Lynn R. Budgeon; et al. (Clinical & Experimental Metastasis, 2004)

Allelic variation at alcohol metabolism genes ( ADH1B , ADH1C , ALDH2 ) and alcohol dependence in an American Indian population - Connie J. Mulligan; Robert W. Robin; Michael V. Osier; Nyamkhishig Sambuughin; Lev G. Goldfarb; Rick A. Kittles; Diane Hesselbrock; David Goldman; Jeffrey C. Long (Human Genetics, 2003)

Functional characterisation of glucose transport in bovine articular chondrocytes - Robin A. J. Windhaber; Robert J. Wilkins; David Meredith (Pflügers Archiv - European Journal of Physiology, 2003)

RNA interference is required for normal centromere function infission yeast - Tom Volpe; Vera Schramke; Georgina L. Hamilton; Sharon A. White; Grace Teng; Robert A. Martienssen; Robin C. Allshire (Chromosome Research, 2003)

Effect of Medium Composition on the Susceptibility of Oral Streptococci to Mercuric Chloride - Rachel Pike; Paul Stapleton; Victoria Lucas; Graham Roberts; Robin Rowbury; Hillary Richards; Peter Mullany; Michael Wilson (Current Microbiology, 2002)

In Vitro Inhibition of Salmonella enterica Serovars Choleraesuis and Typhimurium, Escherichia coli F-18, and Escherichia coli O157:H7 by a Porcine Continuous-Flow Competitive Exclusion Culture - Roger B. Harvey; Robert E. Droleskey; Michael E. Hume; Robin C. Anderson; Kenneth J. Genovese; Kate Andrews; David J. Nisbet (Current Microbiology, 2002)

Shifts in Social Structure of Black Howler (Alouatta pigra) Groups Associated with Natural and Experimental Variation in Population Density - Linde E. T. Ostro; Scott C. Silver; Fred W. Koontz; Robert H. Horwich; Robin Brockett (International Journal of Primatology, 2001)

Kinetic analysis of boron transport in Chara - James C. R. Stangoulis; Robert J. Reid; Patrick H. Brown; Robin D. Graham (Planta, 2001)

CORRECTING AERIAL SURVEY COUNTS OF HARBOR SEALS ( PHOCA VITULINA RICHARDSI ) IN WASHINGTON AND OREGON - Harriet R. Huber; Steven J. Jeffries; Robin F. Brown; Robert L. Delong; Glenn Vanblaricom (Marine Mammal Science, 2001)
A bstract Aerial surveys of harbor seals on land produce only a minimum assessment of the population; a correction factor to account for the missing animals is necessary to estimate total abundance. In 1991 and 1992, VHF radio tags were deployed on harbor seals ( n = 124) at six sites in Washington and Oregon. During aerial surveys a correction factor to account for seals in the water was determined from the proportion of radio‐tagged seals on shore during the pupping season. This proportion ranged from 0.54 to 0.74. Among the six sites there was no significant difference in the proportion of animals on shore nor was there a difference in age/sex categories of seals on shore between sites. The pooled correction factor for determining total population abundance was 1.53. An additional 32 seals were radio tagged in 1993 at one of the sites used in 1991. Comparing data from the two years, we found no interannual variation. Aerial surveys of all known harbor seal haul‐out sites in Washington ( n = 319) and Oregon ( n = 68) were flown during the peak of the pupping season, 1991–1993. The Washington and Oregon harbor seal population was divided into two stocks based on pupping phenology, morphometics, and genetics. Mean counts for the Washington inland stock were 8,710 in 1991, 9,018 in 1992, and 10,092 in 1993. Oregon and Washington coastal stock mean counts were 18,363 in 1991, 18,556 in 1992, and 17,762 in 1993. Multiplying the annual count by the correction factor yielded estimates of harbor seal abundance in the Washington inland stock of 13,326 (95% CI = 11,637–15,259) for 1991, 13,798 (95% CI = 11,980–15,890) for 1992, and 15,440 (95% CI = 13,382–17,814) for 1993. In the Oregon and Washington coastal stock the corrected estimate of harbor seal abundance was 28,094 (95% CI = 24,697–31,960) in 1991, 28,391 (95% CI = 24,847–32,440) for 1992, and 27,175 (95% CI = 23,879–30,926) for 1993.

Resistance to septoria nodorum blotch in the Aegilops tauschii accession RL5271 is controlled by a single gene - Noel E.A. Murphy; Robert Loughman; Robin Wilson; Evans S. Lagudah; Rudi Appels; Michael G.K. Jones (Euphytica, 2000)

The interaction of sarin and soman with plasma proteins: the identification of a novel phosphonylation site - Robin M. Black; John M. Harrison; Robert W. Read (Archives of Toxicology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Acceptable practices in Ontario's forests: Differences between the public and forestry professionals - Robert G. Wagner; James Flynn; C.K. Mertz; Paul Slovic; Robin Gregory (New Forests, 1998)

Towards a Sustainable Paper Cycle: A Summary - Maryanne Grieg‐Gran; Stephen Bass; Joshua Bishop; Sarah Roberts; Richard Sandbrook; Nick Robins; Michael Bazett; Varsha Gadhvi; Susan Subak (Journal of Industrial Ecology, 1997)
Summary The production of paper is a key economic activity accounting in value terms for about 2.5% of the world's industrial production and 2% of world trade. Paper products make a vital contribution to education, communications, packaging, and health care. In recent years the paper cycle has become the focus of environmental concerns about the impacts of forestry pollution from manufacturing, and waste. To address these concerns, the World Business Council for Sustainable Development commissioned the International Institute for Environment and Development (IIED) to examine the sustainability of the paper cycle. The first phase ofthe study involved a review of literature related to the paper cycle to identify the main debates and gaps in knowledge. This was followed by a journal of Industrial Ecology wide‐ranging program of research and consultation on various aspects of the paper cycle. This article summarizes the key findings of the study for different stages of the cycle covering issues such as the impacts of forestry, the outlook for fiber supply, the role of nonwood fiber; the environmental and social impacts of pulp and paper manufacturing, the choice of options for wastepaper and the contribution of the paper cycle to greenhouse gas emissions. The study makes a number of recommendations for the pulp and paper industry, governments, international agencies, consumers, and nongovernmental organizations

New polyester arterial prostheses from great britain: anin vitro andin vivo evaluation - Robert G. Guidoin; Martin King; Michel Marois; Louisette Martin; Daniel Marceau; Robin Hood; Roshan Maini (Annals of Biomedical Engineering, 1986)